Copolymer, its manufacturing method and cured product containing the copolymer
Patent Information
- Application Number
- JP2024558339
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-08-01
- Filing Date
- 2023-12-27
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2043-12-27
AI Technical Summary
【0032】 本発明に係る共重合体は、未硬化の状態であっても低誘電特性に優れ、かつ室温で高い弾性率を示し、硬化性を有する。さらに当該共重合体の硬化体は、優れた低誘電特性、高いガラス転移温度と、室温及び高温で高い弾性率を有するという効果も奏する。共重合体が未硬化状態で上述した特性を満たすと、本共重合体を含む硬化物もまたこれらの特性を満たすこともできる。
Smart Images

Figure 0007652996000001 
Figure 0007652996000002 
Figure 0007652996000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a copolymer, a method for producing the same, and a cured product containing the copolymer. [Background technology]
[0002] As communication frequencies move to the gigahertz band and higher, there is an increasing need for multilayer substrates made of CCL or FCCL containing insulating materials with low dielectric properties. Fluorine-based resins such as perfluoroethylene have the characteristics of excellent low dielectric constant, low dielectric loss, and excellent heat resistance, but they have difficulties in moldability and film formability, and also have issues with adhesion to copper foil in wiring, making them difficult to apply to multilayer substrates. On the other hand, substrates and insulating materials using post-curing resins such as epoxy resin, unsaturated polyester resin, polyimide resin, and phenol resin have been widely used due to their heat resistance and ease of handling, but their dielectric constant and dielectric loss are relatively high, and improvements are needed as insulating materials for high frequencies (Patent Document 1).
[0003] Therefore, attention has been focused on hydrocarbon-based resins that have inherently low dielectric properties. In particular, cyclic olefin-based (co)polymers with high glass transition temperatures (Tg) have been proposed as the main insulating material as a thermoplastic resin (Patent Documents 2 and 3). However, since the glass transition temperature is close to the solder reflow temperature, it is preferable to use a crosslinkable (curable) resin in consideration of process compatibility and process window. In order to turn a hydrocarbon-based resin, which is originally a thermoplastic resin, into a curable resin, it is necessary to introduce a crosslinkable functional group, but functional groups that react with radicals or heat generally have polarity, which deteriorates the low dielectric properties. When attempting to introduce a functional group composed only of hydrocarbons, such as an aromatic vinyl group, in many cases an intermolecular reaction between expensive hydrocarbon-based raw materials is utilized (Patent Document 4), which is often not economical. Patent Document 5 describes an ethylene-olefin (aromatic vinyl compound)-aromatic polyene copolymer obtained from a specific coordination polymerization catalyst and having a specific composition and formulation. BodyA cured body consisting of the above is shown. In the case of this technology, only one of the two vinyl groups of aromatic polyene (divinylbenzene) is selectively copolymerized and the remaining vinyl group is preserved, so that it is easy to obtain a crosslinkable hydrocarbon copolymer macromonomer having an aromatic vinyl functional group. A cured body obtained from a composition of a similar olefin-aromatic vinyl compound-aromatic polyene copolymer and auxiliary raw materials and the like has the characteristics of low dielectric constant and low dielectric loss tangent, and a wide range of physical properties from soft to hard can be given by selecting the composition and appropriate auxiliary raw materials (Patent Documents 6 and 7). However, the specifically described olefin-aromatic vinyl compound-aromatic polyene copolymer is relatively soft, and in order to harden it, it is necessary to blend a large amount of other crosslinkable hard resins or inorganic fillers. Here, the known crosslinkable hard resins have insufficient low dielectric properties, and there is a problem that the low dielectric properties of the cured body decrease when a large amount is blended. When a relatively large amount of inorganic filler is blended, the dielectric constant of the obtained cured body becomes high, especially because inorganic fillers generally have a high dielectric constant. It is important that the cured product is hard and has a high glass transition temperature (Tg), which allows it to have a low coefficient of linear expansion (CTE) in the processing temperature range of the manufacturing process of electronic circuit components, including the solder reflow process, so a hard resin with a higher glass transition temperature is required. Furthermore, insulating materials used in circuit boards, etc. are made by mixing and curing various raw materials such as resins, fillers, and flame retardants, and high compatibility with these raw materials is also required. In particular, resins and flame retardants contain many aromatic groups to obtain stability and flame retardancy at high temperatures, so a crosslinkable hard material that is highly compatible with these is required. For the above reasons, a material that has crosslinkability and whose cured product has excellent low dielectric properties, a high glass transition temperature, and a high elastic modulus at room temperature and high temperatures is required. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 6-192392 [Patent Document 2] International Publication No. 1998 / 56011 [Patent Document 3] JP 2016-037045 A [Patent Document 4] JP 2004-087639 A [Patent Document 5] JP 2007-217706 A [Patent Document 6] International Publication No. 2021 / 112087 [Patent Document 7] International Publication No. 2021 / 112088 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the above-mentioned prior art does not disclose that the α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer in an uncured state has a sufficient level of low dielectric properties, high glass transition temperature, and high elastic modulus. [Means for solving the problem]
[0006] In view of the above-mentioned problems, the present invention aims to provide a novel cross-linkable copolymer (polymer compound) that has low dielectric constant even in an uncured state, a high glass transition temperature, and a high elastic modulus at room temperature and at high temperatures, and a cured product thereof.
[0007] That is, the present invention can provide the following aspects.
[0008] Aspect 1. An α-olefin-cyclic olefin-aromatic polyene copolymer, wherein the copolymer in an uncured state has a dielectric constant of less than 2.4 and a dielectric dissipation factor of less than 0.0008 at a measurement frequency of 40 GHz, and a storage modulus measured at 25°C of 1000 MPa or more. Aspect 2. An α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer, in which the copolymer in an uncured state has a dielectric constant of less than 2.4 and a dielectric dissipation factor of less than 0.0008 at a measurement frequency of 40 GHz, and a storage modulus measured at 25°C of 1000 MPa or more.
[0009] Aspect 3. 3. The copolymer of embodiment 1 or 2, wherein the copolymer in an uncured state has a dielectric constant of less than 2.3 and a dielectric loss tangent of less than 0.0004 at a measurement frequency of 40 GHz.
[0010] Aspect 4. The copolymer according to any one of aspects 1 to 3, wherein the total content of metals derived from the catalyst and the co-catalyst contained in the copolymer is 1000 ppm or less.
[0011] Aspect 5. 5. The copolymer according to any one of aspects 1 to 4, which, when cured alone, exhibits a dielectric constant of less than 3.5 and a dielectric loss tangent of less than 0.001 at a measurement frequency of 40 GHz.
[0012] Aspect 6. 6. The copolymer according to any one of aspects 1 to 5, wherein when cured alone, the cured product has a dielectric constant of less than 2.3 and a dielectric loss tangent of less than 0.0004 at a measurement frequency of 40 GHz.
[0013] Aspect 7. A copolymer according to any one of aspects 1 to 6, which, when cured alone, has a storage modulus of 1 MPa or more as measured at 280° C. of the cured product.
[0014] Aspect 8. A copolymer according to any one of aspects 1 to 7, which, when cured alone, has a storage modulus of 5 MPa or more as measured at 280° C. of the cured product.
[0015] Aspect 9. The copolymer according to any one of aspects 1 to 8, which satisfies all of the following (1) to (2) and (4) to (6): (1) The number average molecular weight of the copolymer is 500 or more and 100,000 or less. (2) The α-olefin unit is an α-olefin having 2 to 20 carbon atoms. (4) The cyclic olefin unit is a cyclic olefin monomer unit having from 10 to 30 carbon atoms, and the content thereof is from 30% by mass to 99% by mass. (5) The aromatic polyene unit is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of vinyl groups and / or vinylene groups derived from the aromatic polyene monomer unit is 2 to 30 per number average molecular weight. (6) The total content of α-olefin units, cyclic olefin units, and aromatic polyene units is 100 mass%.
[0016] Aspect 10. The copolymer according to aspect 2, which satisfies all of the following (1) to (6): (1) The number average molecular weight of the copolymer is 500 or more and 100,000 or less. (2) The α-olefin unit is an α-olefin having 2 to 20 carbon atoms. (3) The aromatic vinyl compound unit is an aromatic vinyl compound having 8 to 20 carbon atoms. (4) The cyclic olefin unit is a cyclic olefin monomer unit having from 10 to 30 carbon atoms, and the content thereof is from 30% by mass to 99% by mass. (5) The aromatic polyene unit is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of vinyl groups and / or vinylene groups derived from the aromatic polyene monomer unit is 2 to 30 per number average molecular weight. (6) The total content of α-olefin units, cyclic olefin units, aromatic vinyl compound units, and aromatic polyene units is 100 mass %.
[0017] Aspect 11. The copolymer according to any one of aspects 1 to 10, wherein the cyclic olefin unit includes at least one selected from the group consisting of norbornene, methylphenylnorbornene, substituted norbornene other than methylphenylnorbornene, and dimethanooctahydronaphthalene.
[0018] Aspect 12. 12. The copolymer according to any one of aspects 1 to 11, having a glass transition temperature in the range of 100° C. or higher and 350° C. or lower.
[0019] Aspect 13. 13. The copolymer according to any one of aspects 1 to 12, having a number average molecular weight of 500 or more and less than 30,000.
[0020] Aspect 14. A method for producing a copolymer according to any one of Aspects 1 to 13, comprising copolymerizing monomers of an α-olefin, a cyclic olefin, and an aromatic polyene, and, if necessary, an aromatic vinyl compound, by coordination polymerization using a coordination polymerization catalyst.
[0021] Aspect 15. A method for producing a copolymer according to aspect 14, wherein the coordination polymerization catalyst is a polymerization catalyst comprising a transition metal compound represented by the following general formula (1) and a co-catalyst: General formula (1) [ka] In the formula, A and B are each independently a group selected from an unsubstituted or substituted cyclopentaphenanthryl group, an unsubstituted or substituted benzoindenyl group, an unsubstituted or substituted cyclopentadienyl group, or an unsubstituted or substituted indenyl group. Y has bonds with A and B, and is a methylene group, a silylene group, an ethylene group, a germylene group, or a boron residue having hydrogen or a hydrocarbon group having 1 to 15 carbon atoms (which may contain 1 to 3 nitrogen, oxygen, sulfur, phosphorus, or silicon atoms) as a substituent. The substituents may be different or the same. Y may have a cyclic structure. X is hydrogen, halogen, an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 10 carbon atoms, an alkylaryl group having 8 to 12 carbon atoms, a silyl group having a hydrocarbon substituent having 1 to 4 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, or a dialkylamide group having an alkyl substituent having 1 to 6 carbon atoms. M is zirconium, hafnium, or titanium.
[0022] Aspect 16. A method for producing a copolymer according to aspect 15, wherein A and B in general formula (1) are each independently a group selected from an unsubstituted or substituted cyclopentadienyl group, or an unsubstituted or substituted indenyl group.
[0023] Aspect 17. 17. The process according to any one of claims 15 to 16, wherein a cocatalyst comprising a boron compound is used.
[0024] Aspect 18. The process of claim 17, wherein the co-catalyst further comprises an aluminum compound.
[0025] Aspect 19. A cured product comprising the copolymer according to any one of aspects 1 to 13.
[0026] Aspect 20. An α-olefin-cyclic olefin-aromatic polyene copolymer satisfying all of the following (1) to (2) and (4) to (6): (1) The number average molecular weight of the copolymer is 500 or more and 100,000 or less. (2) The α-olefin unit is an α-olefin having 2 to 20 carbon atoms. (4) The cyclic olefin unit is a cyclic olefin monomer unit having from 10 to 30 carbon atoms, and the content thereof is from 30% by mass to 99% by mass. (5) The aromatic polyene unit is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of vinyl groups and / or vinylene groups derived from the aromatic polyene monomer unit is 2 to 30 per number average molecular weight. (6) The total content of α-olefin units, cyclic olefin units, and aromatic polyene units is 100 mass%. one or more additive components selected from the group consisting of a resin component, a curing agent, a monomer, a solvent, and a filler; A cured product of a composition comprising: The hardened body has a dielectric constant of 3.5 or less and a dielectric tangent of 0.0015 or less at a measurement frequency of 40 GHz.
[0027] Aspect 21. An α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer that satisfies all of the following (1) to (6); (1) The number average molecular weight of the copolymer is 500 or more and 100,000 or less. (2) The α-olefin unit is an α-olefin having 2 to 20 carbon atoms. (3) The aromatic vinyl compound unit is an aromatic vinyl compound having 8 to 20 carbon atoms. (4) The cyclic olefin unit is a cyclic olefin monomer unit having from 10 to 30 carbon atoms, and the content thereof is from 30% by mass to 99% by mass. (5) The aromatic polyene unit is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of vinyl groups and / or vinylene groups derived from the aromatic polyene monomer unit is 2 to 30 per number average molecular weight. (6) The total content of α-olefin units, cyclic olefin units, aromatic vinyl compound units, and aromatic polyene units is 100 mass %. one or more additive components selected from the group consisting of a resin component, a curing agent, a monomer, a solvent, and a filler; A cured product of a composition comprising: The hardened body has a dielectric constant of 3.5 or less and a dielectric tangent of 0.0015 or less at a measurement frequency of 40 GHz.
[0028] Aspect 22. A cured product according to any one of aspects 19 to 21, further having a storage modulus measured at 25° C. of 1000 MPa or more and a storage modulus measured at 280° C. of 1 MPa or more.
[0029] Aspect 23. The cured product according to any one of aspects 19 to 22, which is an electrical insulating material.
[0030] Aspect 24. A CCL substrate, an FCCL substrate, an interlayer insulating material, a coverlay, a high-frequency transmission circuit, or an antenna, comprising the cured product according to embodiment 23.
[0031] Aspect 25. A method for producing a cured product, comprising the step of polymerizing at least the copolymer according to any one of aspects 1 to 13 with a radical polymerization initiator consisting only of carbon atoms and hydrogen atoms and containing no oxygen or nitrogen atoms in its structure. Effect of the Invention
[0032] The copolymer according to the present invention has excellent low dielectric properties even in an uncured state, and exhibits a high elastic modulus at room temperature and has curability. Furthermore, a cured product of the copolymer has excellent low dielectric properties, a high glass transition temperature, and a high elastic modulus at room temperature and at high temperatures. If the copolymer satisfies the above-mentioned properties in an uncured state, a cured product containing the copolymer can also satisfy these properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] The following is a more detailed description. In this specification, the α-olefin-cyclic olefin-aromatic polyene copolymer is included in the α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer, and may be collectively referred to by the latter name. In this specification, the α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer may be simply referred to as the copolymer of the present invention, or simply as the copolymer. Unless otherwise specified, the numerical range in this specification includes the upper and lower limit values. In this specification, the sheet also includes the concept of a film. In addition, even if the term film is described in this specification, it has the same meaning as a sheet. In addition, even if the term film is described in this specification, it also includes the concept of a sheet. In this specification, the uncured state is defined as a state in which the gel content of the α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer is 20% by mass or less, more strictly 10% by mass or less, and most strictly 5% by mass or less. The gel content is a value obtained by measurement in accordance with JIS K6796:1998 or by measurement in accordance with ASTM D2765-84, which corresponds to ISO10147:1994, which corresponds to JIS.
[0034] In an embodiment of the present invention, an α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer can be provided. The copolymer may have a dielectric constant of less than 2.4, preferably less than 2.3, or 2.0 or more, and a dielectric loss tangent of less than 0.0008, preferably less than 0.0004, more preferably less than 0.0003, and 0.0001 or more, when uncured, at a measurement frequency of 40 GHz. Furthermore, the storage modulus measured at 25°C is 1000 MPa or more. When the copolymer is cured alone, the cured product may have a dielectric constant of less than 3.5, a dielectric loss tangent of less than 0.0010, preferably a dielectric constant of 2.0 or more and less than 3.5, and a dielectric loss tangent of 0.0001 or more and less than 0.0010, more preferably a dielectric constant of less than 2.4, 2.0 or more, and a dielectric loss tangent of less than 0.0004, and most preferably a dielectric constant of less than 2.3, and a dielectric loss tangent of less than 0.0003, and 0.0001 or more. Furthermore, the storage modulus may be 1000 MPa or more as measured at 25° C. Furthermore, the storage modulus of the cured product as measured at 280° C. is preferably 1 MPa or more, and more preferably 5 MPa or more.
[0035] In another embodiment, it is also possible to provide an embodiment in which the dielectric constant or dielectric tangent in the uncured state does not satisfy the above conditions, but the dielectric constant, dielectric tangent, and storage modulus of the cured product satisfy the above conditions.
[0036] <α-olefin-cyclic olefin-aromatic polyene copolymer> Furthermore, the α-olefin-cyclic olefin-aromatic polyene copolymer of the present invention is a copolymer having each monomer unit of α-olefin, cyclic olefin, and aromatic polyene, and its production method is arbitrary. Preferably, the α-olefin-cyclic olefin-aromatic polyene copolymer is a copolymer that satisfies all of the following (1) to (2) and (4) to (6). (1) The number average molecular weight of the copolymer is 500 or more and 100,000 or less. (2) The α-olefin unit is an α-olefin having 2 to 20 carbon atoms. (4) The cyclic olefin unit is a cyclic olefin monomer having from 10 to 30 carbon atoms which may have an aromatic ring, and the content thereof is from 30% by mass to 99% by mass. (5) The aromatic polyene unit is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of vinyl groups and / or vinylene groups derived from the aromatic polyene monomer unit is 2 to 30 or 2 to less than 30 per number average molecular weight. (6) The total content of the monomer units of the α-olefin, cyclic olefin, and aromatic polyene is 100 mass %.
[0037] The present α-olefin-cyclic olefin-aromatic polyene copolymer can be obtained by copolymerizing each of the monomers of an α-olefin, a cyclic olefin, and an aromatic polyene.
[0038] <α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer> In some embodiments of the present invention, it is preferred to use an aromatic vinyl compound to obtain an α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer. In this specification, the α-olefin-cyclic olefin-aromatic polyene copolymer is included in the α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer, and may be referred to collectively by the latter name. Furthermore, the α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer of the present invention is a copolymer having each monomer unit of α-olefin, cyclic olefin, aromatic vinyl compound, and aromatic polyene, and its production method is arbitrary. Preferably, the α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer is a copolymer that satisfies all of the following (1) to (6). (1) The number average molecular weight of the copolymer is 500 or more and 100,000 or less. (2) The α-olefin unit is an α-olefin having 2 to 20 carbon atoms. (3) The aromatic vinyl compound unit is an aromatic vinyl compound having 8 to 20 carbon atoms. (4) The cyclic olefin unit is a cyclic olefin monomer having from 10 to 30 carbon atoms which may have an aromatic ring, and the content thereof is from 30% by mass to 99% by mass. (5) The aromatic polyene unit is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of vinyl groups and / or vinylene groups derived from the aromatic polyene monomer unit is 2 to 30 or 2 to less than 30 per number average molecular weight. (6) The total content of the monomer units of the α-olefin, the cyclic olefin, the aromatic vinyl compound, and the aromatic polyene is 100 mass %.
[0039] The present α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer can be obtained by copolymerizing each of the monomers of α-olefin, cyclic olefin, aromatic vinyl compound, and aromatic polyene.
[0040] The α-olefin monomer is an α-olefin having 2 to 20 carbon atoms, such as ethylene, propylene, 1-butene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 4-methyl-1-pentene, and 3,5,5-trimethyl-1-hexene, and is most preferably ethylene. In the present copolymer, the α-olefin content is arbitrary, but is preferably 0% by mass or more and 40% by mass or less, more preferably more than 0% by mass or more and 30% by mass or less, even more preferably 1% by mass or more and 30% by mass or less, and most preferably 5% by mass or more and 30% by mass or less. When the α-olefin monomer unit content is 40% by mass or less, the content of cyclic olefin units is relatively high, and the glass transition temperature of the copolymer can be set within a preferred range. The higher the α-olefin monomer unit content (for example, 5% by mass or more), the less brittle the copolymer or its cured product becomes.
[0041] In this specification, the cyclic olefin monomer refers to a cyclic olefin having 7 to 30 carbon atoms (preferably 10 to 30 carbon atoms). The cyclic olefin having 7 to 30 carbon atoms is a cyclic olefin having one or more alicyclic structures in the molecule and having a polymerizable vinyl group, vinylene group, or vinylidene group. A preferred cyclic olefin is a cyclic olefin having a hydrocarbon ring structure without heteroatoms, and more preferably a cyclic olefin having an unsaturated hydrocarbon ring. Such cyclic olefins have the notable characteristics of low dielectric properties and high glass transition temperature, while being easily prepared using inexpensive raw materials and simple processes compared to conventional engineering plastics. An example of such a cyclic olefin is norbornenes. Norbornenes are monomers selected from norbornene and substituted norbornene. Norbornene can be synthesized, for example, by the Diels-Alder reaction of ethylene and cyclopentadiene. The substituted norbornene is a substituted norbornene having a polymerizable vinyl group, vinylene group, or vinylidene group in the molecule, and examples thereof include dimethanooctahydronaphthalene (DMON) and trimethanododecahydroanthracene (TMDA). These are also Diels-Alder reaction products of norbornenes and cyclopentadiene. These substituted norbornenes are specifically described, for example, in International Publication No. 2006 / 118261. In the present invention, more preferred cyclic olefins are cyclic olefins having a larger number of ring structures and a higher molecular weight, such as dimethanooctahydronaphthalene (DMON) and trimethanododecahydroanthracene (TMDA). When such cyclic olefins are copolymerized, a copolymer with a higher glass transition temperature (Tg) can be obtained with a smaller mol% content of the monomer unit. Therefore, it is possible to increase the mol% content of other monomer units while maintaining the high glass transition temperature of the copolymer. Increasing the mole percent content of aromatic vinyl compound monomer units as other monomer units is preferable because it enhances the aromatic properties of the copolymer as a whole and increases the compatibility of the copolymer with other raw materials and resins.These high molecular weight cyclic olefins may be used alone or may be copolymerized as a mixture with norbornene or the like. In particular, the above-mentioned DMON and TMDA may be obtained as a mixture with norbornene when produced by Diels-Alder reaction, and the production cost can be reduced by using the mixture as it is for polymerization. In the present invention, more preferred cyclic olefins are norbornenes having aromatic substituents, such as phenylnorbornene (5-phenylbicyclo[2.2.1]hept-2-ene), which is a Diels-Alder reaction product of cyclopentadiene and styrene, indanylnorbornene (1,4-methano-1,9a,4,4a-tetrahydrofluorene), which is a Diels-Alder reaction product of cyclopentadiene and indene, and methylphenylnorbornene (MPNB, 5-methyl-5-phenylbicyclo[2.2.1]hept-2-ene), which is a Diels-Alder reaction product of cyclopentadiene and α-methylstyrene. Such norbornenes having aromatic substituents can give the copolymer a higher glass transition temperature (Tg) when copolymerized, and furthermore, because they exhibit aromaticity, they can exhibit high compatibility with other aromatic raw materials (crosslinkable soft resins and flame retardants). Furthermore, the use of methylphenylnorbornene (5-methyl-5-phenylbicyclo[2.2.1]hept-2-ene) is preferable because it can improve the thermal oxidation resistance of the copolymer obtained, as described in JP-A-2005-239975. Norbornenes having these aromatic substituents are specifically described, for example, in JP-A-11-504669 and JP-A-2005-239975. The optimal content of the cyclic olefin unit contained in the copolymer varies depending on the type of cyclic olefin, but is, for example, 50% by mass or more and 99% by mass or less, preferably 50% by mass or more and 95% by mass or less, more preferably 70% by mass or more and 95% by mass or less, and most preferably 80% by mass or more and 95% by mass or less. The optimum content of the cyclic olefin unit contained in the present copolymer may be less than 90% by mass from the viewpoint of imparting a certain degree of toughness to the copolymer. The content in this range makes it easy to achieve a preferred high glass transition temperature of the copolymer.The glass transition temperature of the copolymer is preferably 100° C. or more and 350° C. or less, more preferably 130° C. or more and 300° C. or less, and most preferably 180° C. or more and 300° C. or less. Those skilled in the art can appropriately adjust the type and content of the cyclic olefin used to achieve this preferred glass transition temperature.
[0042] In a preferred embodiment, the cyclic olefin unit contained in the copolymer may include one or more selected from the group consisting of norbornene, methylphenylnorbornene, substituted norbornene other than methylphenylnorbornene, and dimethanooctahydronaphthalene, and more preferably, may include one or more selected from the group consisting of norbornene, methylphenylnorbornene, and dimethanooctahydronaphthalene.
[0043] The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and examples thereof include styrene, paramethylstyrene, ethylvinylbenzene, paraisobutylstyrene, various vinylnaphthalenes, and various vinylanthracenes. The aromatic vinyl compound may be copolymerized with components contained as impurities in the aromatic polyene used in polymerization, and may be contained in the copolymer as a result. The content of the aromatic vinyl compound monomer unit contained in the copolymer is arbitrary, but is preferably 0% by mass or more and 40% by mass or less, more preferably 0% by mass or more and 30% by mass or less, even more preferably 0% by mass or more and 20% by mass or less, still more preferably 0% by mass or more and 10% by mass or less, and even more preferably 0% by mass. The content of the aromatic vinyl compound monomer unit contained in the copolymer may exceed 0% by mass. The content of the aromatic vinyl compound monomer unit contained in the copolymer may be 30% by mass or less, may be less than 30% by mass, may be 10% by mass or less, may be less than 10%, may be 1% by mass or less, may be less than 1% by mass, or may be less than 0.5% by mass.
[0044] When the content of aromatic vinyl compound monomer units is 40% by mass or less, the content of cyclic olefin units is relatively high, and the glass transition temperature of the copolymer can be increased. On the other hand, when the content of aromatic vinyl compound monomer units is 10% by mass or more, preferably 30% by mass or more, it is possible to improve the aromaticity of the copolymer, particularly when the cyclic olefin of the copolymer of the present invention does not have an aromatic substituent, and it is preferable that the compatibility with other resin materials, flame retardants, and fillers is improved, the flame retardant is suppressed from bleeding out, and it is easy to highly fill the filler. As described above, the glass transition temperature and aromaticity of the copolymer can be adjusted by the aromatic vinyl compound content of the copolymer.
[0045] The aromatic polyene monomer is a polyene having 5 to 20 carbon atoms and having multiple vinyl groups and / or vinylene groups in its molecule, preferably a polyene having 8 to 20 carbon atoms. The aromatic polyene monomer is preferably a polyene having 8 to 20 carbon atoms and having multiple vinyl groups in its molecule, more preferably a compound having an aromatic vinyl structure such as ortho-, meta-, or para-various divinylbenzenes or mixtures thereof, divinylnaphthalene, divinylanthracene, p-2-propenylstyrene, or p-3-butenylstyrene, which is substantially free of oxygen, nitrogen, or halogen and is composed of carbon and hydrogen. In addition, a bifunctional aromatic vinyl compound described in JP-A-2004-087639, for example, 1,2-bis(vinylphenyl)ethane (abbreviation: BVPE), can also be used. Among these, preferably, ortho-, meta-, or para-various divinylbenzenes or mixtures thereof are used, and most preferably, a mixture of meta- and para-divinylbenzene is used. In this specification, these divinylbenzenes are referred to as "divinylbenzenes." When divinylbenzenes are used as aromatic polyenes, the vinyl groups contained in the divinylbenzene units are preferred because they have high crosslinking efficiency during curing treatment and facilitate curing.
[0046] The number average molecular weight of the copolymer is preferably 500 to 100,000, more preferably 500 to 30,000 or less than 30,000, more preferably 500 to 15,000 or less than 15,000, and even more preferably 500 to 12,000 or less than 12,000. When the number average molecular weight is 500 or more, the mechanical properties of the composition in the uncured stage are high, and the adhesiveness is moderate, so that the molding process as a thermoplastic resin is easy to be obtained. When the number average molecular weight is 30,000 or less, the molding processability is improved. In particular, it is convenient that the number average molecular weight is 30,000 or less or 12,000 or less, because the viscosity of the varnish containing the copolymer can be kept below a certain value. When the viscosity of the varnish is lower than a certain value, the workability is improved, and the varnish is easily impregnated into glass fibers, etc., and the embedding property for semiconductor devices having uneven surfaces is improved.
[0047] In the copolymer, the content of vinyl groups and / or vinylene groups derived from aromatic polyene units is 2 to 30, preferably 3 to 20 per number average molecular weight. The content of vinyl groups and / or vinylene groups derived from aromatic polyene units may be less than 30, preferably less than 20 per number average molecular weight. The content of vinyl groups and / or vinylene groups may be collectively referred to as "vinyl group content" below. Since vinyl groups are superior to vinylene groups in terms of crosslinking efficiency, the content of vinyl groups (not including vinylene groups in this case) derived from aromatic polyene units is preferably 2 to 30, preferably 3 to 20 per number average molecular weight in the present invention. When the vinyl group content is 2 or more, the crosslinking efficiency is high and a cured body with sufficient crosslinking density can be obtained. When the vinyl group content is increased, it becomes easier to improve the mechanical properties of the finally obtained cured body at room temperature and high temperature. The vinyl group content derived from aromatic polyene units (divinylbenzene units) per number average molecular weight in the copolymer is determined by the number average molecular weight (Mn) calculated in terms of standard polystyrene obtained by a GPC (gel permeation chromatography) method known to those skilled in the art, and 1H-NMR measurements and / or quantitative mode 13 The composition obtained by C-NMR measurement can be compared with the vinyl group content derived from the aromatic polyene unit. Such a method is obvious and well known to those skilled in the art. It can also be achieved by a method described in the patent documents in the prior art literature of this specification. The content of aromatic polyene monomer units in the copolymer is arbitrary, but is preferably less than 40% by mass, more preferably less than 30% by mass. At such a content, the number of crosslinking groups is appropriately suppressed, and the effect of improving the stability during the production of the copolymer and the stability during curing is obtained.
[0048] In the present copolymer, the α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer may, specifically, be one or more of the group consisting of propylene-norbornene-styrene-divinylbenzene copolymer, 1-hexene-norbornene-styrene-divinylbenzene copolymer, 1-octene-norbornene-styrene-divinylbenzene copolymer, ethylene-norbornene-ethylvinylbenzene-divinylbenzene copolymer, propylene-styrene-norbornene-divinylbenzene copolymer, 1-hexenestyrene-styrene-norbornene-divinylbenzene copolymer, and 1-octene-norbornene-styrene-divinylbenzene copolymer. Further, copolymers in which the above-mentioned norbornene is replaced with dimethanooctahydronaphthalene (DMON), trimethanododecahydroanthracene (TMDA), phenylnorbornene (5-phenylbicyclo[2.2.1]hept-2-ene), or methylphenylnorbornene (5-methyl-5-phenylbicyclo[2.2.1]hept-2-ene) are also suitable examples of the copolymers of the present invention.
[0049] In the α-olefin-cyclic olefin-aromatic polyene copolymer or α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer according to a certain embodiment, the content of α-olefin monomer units can be 0% by mass (i.e., no α-olefin monomer units are included). Such a copolymer is also referred to as a "cyclic olefin-aromatic polyene copolymer" or a "cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer" in this specification. The copolymer according to this embodiment will be described below. Here, the types of each monomer of the cyclic olefin, aromatic vinyl compound, and aromatic polyene, and the content of each monomer unit in the copolymer are as described above.
[0050] The above cyclic olefin-aromatic polyene copolymer or cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer can be produced by the production method described herein. Specifically, it can be produced from each monomer of a cyclic olefin, an aromatic vinyl compound, and an aromatic polyene using a coordination polymerization catalyst consisting of a transition metal compound and a cocatalyst. The chemical structure of the present copolymer obtained using a coordination polymerization catalyst consisting of a combination of a transition metal compound and a cocatalyst is characterized in that it does not contain a specific structure. That is, while conventional copolymers obtained by cationic polymerization methods according to the prior art have a characteristic polymer end structure as described in, for example, International Publication No. 2018 / 181842, the copolymer according to the embodiment of the present invention has a notable difference in that it does not have such a structure. Due to this difference, the present invention has the effect of facilitating molecular design.
[0051] The polymer end structure contained in the cyclic olefin-aromatic polyene copolymer or the cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer is 1 H-NMR, 13It can be qualitatively or quantitatively clarified by a known method using C-NMR. As a typical example of the copolymer, the polymer end structure contained in the cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer composed of norbornene, DMON, MPNB as the cyclic olefin, styrene or ethylvinylbenzene as the aromatic vinyl compound, and divinylbenzene as the aromatic polyene is substantially one of the structures represented by E-1 to E-8 below, or any combination thereof. In the case of a cyclic olefin other than the above, an aromatic vinyl compound other than the above, or an aromatic polyene other than divinylbenzene, these structural formulas can be understood by reading them as structures corresponding to these. "Substantially" indicates that 90 mol% or more, preferably 95 mol% or more, and most preferably 99 mol% or more of the total end structures of the copolymer are one of the structures represented by E-1 to E-8 below, or any combination thereof.
[0052] [ka]
[0053] In the above formula, P represents a polymer structural residue of norbornene (or DMNO, or MPNB)-styrene (or ethylvinylbenzene)-divinylbenzene copolymer, and Z represents hydrogen, an ethyl group, or a vinyl group.
[0054] When the cyclic olefin is DMON or MPNB, the structure including the substituents R1 and R2 is as shown below.
[0055] [ka]
[0056] The polymerization initiation terminals, which account for about half of the polymer terminal structures, are generally the above-mentioned E-1, E-2, E-4, and E-5. These structures are terminals with saturated structures, and therefore aromatic vinyl compound-aromatic polyene copolymers are essentially characterized by high durability such as heat resistance. The ratio of the polymerization initiation terminal structure varies depending on various factors, such as whether the first monomer insertion occurs into a metal-hydrogen bond, whether the first monomer insertion occurs into a metal-alkyl group structure, whether the first monomer insertion occurs from a cyclic olefin, styrene, or divinylbenzene, and whether the first monomer is 2,1 insertion or 1,2 insertion when styrene or divinylbenzene is used.
[0057] Among the polymer end structures, the structures of the chain transfer ends (also called polymerization termination ends) of the polymer growing chain are generally E-1, E-6, and E-8 in large numbers, but also E-3, E-4, and E-7. The proportion of the chain transfer end structure can vary depending on whether the chain transfer occurs by hydrogen abstraction at the beta position, by chain transfer to another coordination monomer, by chain transfer to an alkylaluminum which is a cocatalyst component, or by chain transfer to a chain transfer agent such as hydrogen. In general, cyclic olefins have a rigid structure, so there are few E-3 structures due to hydrogen abstraction at the beta position.
[0058] The polymer end structure of the above cyclic olefin-aromatic polyene copolymer or cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer is composed of at least one of the above structures E-1 to E-8, and does not substantially contain other structures. The aromatic vinyl compound-aromatic polyene copolymer which may contain an olefin according to the present invention is obtained by a specific coordination polymerization, and is therefore a copolymer with a relatively low degree of polymer chain branching and high linearity, and the proportion of the polymer end structure contained is also relatively small.
[0059] An example of a polymer obtained by cationic polymerization according to the prior art will be described below in comparison with the present invention. The characteristic terminal structure (structures indicated as t1 and t2 in WO 2018 / 181842) formed by chain transfer such as electrophilic substitution reaction of the carbocation at the polymer growth end to an aromatic monomer or an aromatic ring contained in the polymer itself, which is described in WO 2018 / 181842 according to the prior art, is not included in the copolymer according to the present invention. On the other hand, the aromatic vinyl compound-aromatic polyene copolymer according to the prior art described in WO 2018 / 181842 contains a very large number of terminal structures per polymer molecule due to its dendritic, multi-branched structure, and the terminal structures described therein are mostly unsaturated structures of vinyl groups and vinylene groups with various structures due to cationic polymerization, which causes problems with heat resistance stability, and in particular, the vinylene groups contained in a relatively large amount remain in the cured body even after the curing reaction, which deteriorates the heat resistance stability after curing. That is, if a large number of unsaturated groups such as vinylene groups are present in the cured product, they will bond with or react with oxygen in the air, undesirably increasing the dielectric constant and dielectric tangent of the cured product.
[0060] Furthermore, JP 2018-39995 A also describes a cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer according to the prior art, which is obtained by a similar cationic polymerization. Although the patent document does not describe the terminal structure, the same manufacturing method as WO 2018 / 181842 is adopted, and the majority of the obtained polymer is composed of aromatic polyene and aromatic vinyl compound units and contains a high content of aromatic polyene (divinylbenzene) units, and the molecular weight distribution (Mw / Mn) is similarly large, so it is considered that it has a terminal structure similar to that described in WO 2018 / 181842 and has a dendritic multi-branched structure. Since it has a cyclic olefin structure as part of its terminal structure, it is possible to reduce the proportion of unsaturated groups at the terminal, and the increase rate of the dielectric constant and dielectric loss tangent after heat resistance test is also reduced compared to the case where the cyclic olefin is not included, but it is still considered to be insufficient. In contrast to the dendritic structure having many terminal groups according to such conventional techniques, the copolymer of the present invention has a relatively linear structure, and the number of terminal structures in one copolymer molecule is small. Furthermore, cyclic olefins are not unevenly distributed at the terminals of the copolymer, so that the number of cyclic olefin terminals contained in one copolymer molecule can generally be less than 1.5.
[0061] When the α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer of the present invention is cured alone, it can be sufficiently cured. Here, curing alone means adding a curing agent (peroxide or other radical polymerization initiator) in an amount of 1 part by mass or less to 100 parts by mass of the copolymer, and performing a curing treatment under curing conditions appropriate for the peroxide used. The degree of curing can be evaluated by the gel content, which is higher than 50%, preferably 90% or more, and particularly preferably 95% or more. The cured product exhibits excellent low dielectric properties and has a high glass transition temperature, and a cured product having a high elastic modulus at room temperature and high temperatures can be obtained. Specifically, the dielectric constant of the cured product may be 3.5 or less, preferably 2.0 to 3.5, more preferably 2.0 to less than 3.5, and even more preferably 2.0 to less than 2.5. The dielectric loss tangent of the cured product may be less than 0.001, preferably 0.0002 to less than 0.001, and substantially 0.0005 to less than 0.001. The glass transition temperature is arbitrary, but can be 100°C or more and 350°C or less, preferably 130°C or more and 300°C or less. The storage modulus measured at 25°C can be 1000MPa or more, and the storage modulus measured at 280°C can be 1MPa or more, more preferably 5MPa or more. Here, the gel content is a value obtained in accordance with the above-mentioned JIS K6796:1998 (or ASTM D2765-84 corresponding to ISO10147:1994 corresponding to the JIS), and the dielectric constant and dielectric dissipation factor are values obtained at 25°C and 40GHz. The glass transition temperature and the storage modulus at each temperature are obtained by dynamic mechanical analysis (DMA) at a measurement frequency of 1Hz. Therefore, it is possible to obtain a cured product with a sufficiently high gel content by curing a composition containing this copolymer, and the cured product can exhibit excellent low dielectric properties, a high glass transition temperature, and a high storage modulus at room temperature and high temperatures.
[0062] <Composition containing the copolymer of the present invention> The copolymer of the present invention can be cured alone, but it may also be combined with other materials to form a composition, and the composition can be cured. Here, the other materials include the following "resin component," "curing agent," "monomer," "other olefin-aromatic vinyl compound-aromatic polyene copolymer not containing cyclic olefin," "solvent," "filler," "other additives," etc.
[0063] <Resin component> As the resin component, any resin may be used as long as it does not impair the effects of the present invention, but preferably one or more selected from a hydrocarbon-based elastomer, a polyether-based resin, an aromatic polyene-based resin, and an olefin-aromatic vinyl compound-aromatic polyene copolymer not containing a cyclic olefin may be used. Among these, a hydrocarbon-based elastomer and an olefin-aromatic vinyl compound-aromatic polyene copolymer not containing a cyclic olefin are more preferable. Among the hydrocarbon-based elastomers, a conjugated diene polymer is preferable. Among the conjugated diene polymers, 1,2-polybutadiene is preferable. The amount of the resin component may be preferably in the range of 1 to 500 parts by mass in total, more preferably 1 to 300 parts by mass in total, based on 100 parts by mass of the copolymer of the present invention.
[0064] <Hydrocarbon elastomer> The number average molecular weight of the hydrocarbon elastomer that can be suitably used in the composition of the present invention may be 20,000 or more, preferably 30,000 or more. Examples of the hydrocarbon elastomer include single or multiple elastomers selected from ethylene or propylene elastomers, conjugated diene polymers, block or random copolymers of aromatic vinyl compounds-conjugated dienes, and hydrogenated products thereof. Examples of the ethylene elastomers include ethylene-α-olefin copolymers such as ethylene-octene copolymers and ethylene-1-hexene copolymers, EPR, and EPDM. Examples of the propylene elastomers include atactic polypropylene, low stereoregular polypropylene, and propylene-α-olefin copolymers such as propylene-1-butene copolymer. The above-mentioned hydrocarbon elastomers may be modified by introducing functional groups with maleic anhydride or other compounds.
[0065] <Conjugated diene polymer> Examples of the conjugated diene polymer include polybutadiene and 1,2-polybutadiene. Examples of the aromatic vinyl compound-conjugated diene block or random copolymer and their hydrogenated products (hydrogenated products) include SBS, SIS, SEBS, SEPS, SEEPS, SEEBS, etc. 1,2-polybutadiene that can be suitably used is available as a product of JSR Corporation, and is also available from Nippon Soda Co., Ltd. under the product names of liquid polybutadiene: B-1000, 2000, and 3000. Examples of the copolymer containing a 1,2-polybutadiene structure that can be suitably used include "Ricon 100" from TOTAL CRAY VALLEY. The above-mentioned conjugated diene polymers and their hydrogenated products may be modified, for example, by introducing functional groups with maleic anhydride or other compounds. Among the conjugated diene polymers, conjugated diene copolymers are preferred. Among these conjugated diene copolymers, hydrogenated block copolymers such as SEBS, SEPS, SEEPS, and SEEBS are useful as compatibilizers between the copolymer of the present invention and other <resin components>. These are available from Asahi Kasei under the trade names Tuftec or SOE-SS, from Kuraray under the trade name Septon, and from KRATON under the trade name Kraton.
[0066] <Polyether resin> Examples of polyether-based resins include polyphenylene ether and polyether. As polyphenylene ether having a functional group, it is preferable that the molecular end is modified with a functional group. In addition, when the polyphenylene ether is added for the purpose of curing the composition of the present invention, it is preferable that the polyphenylene ether has a plurality of functional groups in one molecule. For example, it is preferable to use modified polyphenylene ether. Examples of the functional group include a radically polymerizable functional group, an epoxy group, and the like, and it is preferably a radically polymerizable functional group. As the radically polymerizable functional group, a vinyl group is preferable. As the vinyl group, one or more of the group consisting of an allyl group, a (meth)acryloyl group, and an aromatic vinyl group are preferable, one or more of the group consisting of a (meth)acryloyl group and an aromatic vinyl group are more preferable, and an aromatic vinyl group is most preferable. That is, in the composition of the present invention, a bifunctional polyphenylene ether in which both ends of the molecular chain are modified with a radically polymerizable functional group is particularly preferable. Examples of such polyphenylene ethers include Noryl (trademark) SA9000 (modified polyphenylene ether having methacryloyl groups at both ends, number average molecular weight 2200) manufactured by SABIC and bifunctional polyphenylene ether oligomer (OPE-2St, modified polyphenylene ether having vinylbenzyl groups at both ends, number average molecular weight 1200) manufactured by Mitsubishi Gas Chemical Co., Ltd. In addition, allylated PPE manufactured by Asahi Kasei Corporation and aromatic polyether (ELPAC HC-F series) manufactured by JSR Corporation can also be used. Among these, it is preferable to use bifunctional polyphenylene ether oligomer (OPE-2St) manufactured by Mitsubishi Gas Chemical Co., Ltd. and aromatic polyether (ELPAC HC-F series) manufactured by JSR Corporation.
[0067] <Aromatic polyene resin> The aromatic polyene resin includes a divinylbenzene reactive hyperbranched copolymer (PDV or ODV) manufactured by Nippon Steel Chemical & Material Co., Ltd. Such a copolymer is described, for example, in the document "Synthesis of polyfunctional aromatic vinyl copolymer and development of a new IPN type low dielectric loss material using the same" (Kawabe Masanao et al., Journal of Electronics Packaging Society, p. 125, Vol. 12 No. 2 (2009)).
[0068] <Another olefin-aromatic vinyl compound-aromatic polyene copolymer not containing cyclic olefin> Another olefin-aromatic vinyl compound-aromatic polyene copolymer not containing a cyclic olefin that can be used in the present invention is an olefin-aromatic vinyl compound-aromatic polyene copolymer that satisfies all of the following (A) to (E). (A) The number average molecular weight of the copolymer is 500 or more and 100,000 or less. (B) The olefin monomer unit is one or more α-olefins selected from α-olefins having from 2 to 20 carbon atoms, and the olefins do not include cyclic olefins. (C) The aromatic vinyl compound monomer unit is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0 to 90 mass %. (D) The aromatic polyene monomer unit is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene unit per number average molecular weight is 2 to 30. The content of the vinyl groups and / or vinylene groups derived from the aromatic polyene unit per number average molecular weight may be 2 to less than 30. (E) The total amount of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100 mass %. Details of the α-olefin, aromatic vinyl compound, and aromatic polyene monomers are as described above. Such copolymers are specifically described in JP 2009-161743 A, WO 2021 / 112087, WO 2021 / 112088, and WO 2022 / 014599. However, as described above, such other copolymers do not contain cyclic olefins. Among olefin-aromatic vinyl compound-aromatic polyene copolymers that do not contain cyclic olefins, copolymers having an aromatic vinyl compound monomer content of 0 to 60% by mass are particularly soft, and therefore are preferably blended with the copolymer of the present invention to improve the toughness of the resulting cured body and suppress cracking.
[0069] <Hardening agent> The curing agent that may be contained in the composition may be a known curing agent that can be used for the polymerization or curing of conventional aromatic polyenes and aromatic vinyl compounds. Examples of such curing agents include radical polymerization initiators, cationic polymerization initiators, and anionic polymerization initiators, and preferably radical polymerization initiators can be used. Preferred are organic peroxides and azo polymerization initiators, which can be freely selected depending on the application and conditions. A catalog listing organic peroxides can be found on the NOF Corporation website, for example: https: / / www.nof.co.jp / product-search / family / 1020001 It can be downloaded from. Organic peroxides are also described in the catalogs of Fujifilm Wako Pure Chemical Industries, Ltd. and Tokyo Chemical Industry Co., Ltd. The curing agent used in the present invention can be obtained from these companies. Furthermore, a hydrocarbon-based radical polymerization initiator that does not contain oxygen atoms or nitrogen atoms in the structure, i.e., composed only of carbon atoms and hydrogen atoms, such as 2,3-dimethyl-2,3-diphenylbutane, can also be suitably used. When a cured body is produced using such a hydrocarbon-based radical polymerization initiator, a cured body that does not contain oxygen atoms or nitrogen atoms and has a lower dielectric constant and dielectric loss tangent can be obtained, and the low dielectric properties of the cured body can be further improved. In addition, a known photopolymerization initiator that uses light, ultraviolet rays, or radiation can also be used as a curing agent. Examples of curing agents that use a photopolymerization initiator include a photoradical polymerization initiator, a photocationic polymerization initiator, and a photoanionic polymerization initiator. Such a photopolymerization initiator can be obtained, for example, from Tokyo Chemical Industry Co., Ltd. Furthermore, curing by radiation or an electron beam itself is also possible. It is also possible to perform crosslinking and curing by thermal polymerization of the raw materials contained without containing a curing agent.
[0070] There is no particular limit to the amount of the curing agent used, but generally, 0.01 to 10 parts by mass is preferred per 100 parts by mass of the composition (preferably excluding the curing agent and solvent). When using a curing agent such as a peroxide or azo polymerization initiator, the curing process is carried out at an appropriate temperature and time, taking into account its half-life. In this case, the conditions are arbitrary according to the curing agent, but generally, a temperature range of about 50°C to 180°C is appropriate.
[0071] <Monomer> The amount of the monomer that may be contained in the composition of the present invention is arbitrary, but is preferably 300 parts by mass or less relative to 100 parts by mass of the copolymer. The composition may not substantially contain a monomer. When the monomer is contained, the amount is preferably 1 part by mass or more, more preferably 5 parts by mass or more. In particular, when the monomer is 30 parts by mass or less, the uncured composition is less likely to have a viscous property, and molding processing as a thermoplastic resin becomes easier. In addition, when the content of the easily volatile monomer is below a certain level, odor at the uncured stage does not become a problem. When a solvent is added to the composition to make the product into a varnish-like form, there is a problem that the monomer is lost with the evaporation of the solvent during use, and the substantial content of the monomer is easily reduced. In addition, when the product is in the form of an uncured sheet, if the monomer contains a certain amount or less, the content of the monomer is less likely to change during storage. The monomer that can be suitably used in the composition of the present invention preferably has a molecular weight of less than 1000, more preferably less than 500. Monomers that can be suitably used in the composition of the present invention are the aromatic vinyl compound monomers, the aromatic polyene monomers, the aromatic vinylene monomers described below, and / or the polar monomers described below. As the monomer, a monomer that can be polymerized by a radical polymerization initiator is preferred, and one or more of the group consisting of aromatic vinyl compounds and aromatic polyenes is more preferred. In addition, BVPE (1,2-bis(vinylphenyl)ethane) described in JP-A-2003-212941 can also be suitably used.
[0072] <Aromatic vinylene monomer> The aromatic vinylene monomer that may be included in the present invention refers to a compound having both a single aromatic ring or multiple condensed aromatic rings having 9 to 30 carbon atoms and a vinylene group. Examples of such aromatic vinylene compounds include indenes, beta-substituted styrenes, and acenaphthylenes. Examples of indenes include indene, various alkyl-substituted indenes, and phenyl-substituted indenes. Examples of beta-substituted styrenes include beta-alkyl-substituted styrenes such as beta-methylstyrene, and phenyl-substituted styrenes. Examples of acenaphthylenes include acenaphthylene, various alkyl-substituted acenaphthylenes, and various phenyl-substituted acenaphthylenes. As the aromatic vinylene compound, the above-exemplified compounds may be used alone or in combination of two or more. From the viewpoints of industrial availability and radical polymerizability, acenaphthylene is the most preferable aromatic vinylene compound.
[0073] <Polar monomer> A relatively small amount of polar monomer can be used for the purpose of imparting adhesion to other materials required as an insulating material. Examples of the polar monomer include various maleimides, bismaleimides, maleic anhydride, glycidyl (meth)acrylate, triallyl isocyanurate, tri(meth)acrylic isocyanurate, trimethylolpropane tri(meth)acrylate, and the like. Maleimides and bismaleimides that can be used in the present invention are described in, for example, International Publication No. 2016 / 114287 and can be purchased, for example, from Daiwa Kasei Co., Ltd. These maleimide group-containing compounds may be used as polyamino bismaleimide compounds from the viewpoints of solubility in organic solvents, high frequency characteristics, high adhesion to conductors, moldability of prepregs, and the like. The polyamino bismaleimide compound can be obtained, for example, by subjecting a compound having two maleimide groups at the terminals to a Michael addition reaction with an aromatic diamine compound having two primary amino groups in the molecule. When attempting to obtain high crosslinking efficiency with the addition of a small amount, it is preferable to use a polar monomer having a multifunctional group of two or more functional groups, and examples of such a monomer include bismaleimides, triallyl isocyanurate (TAIC), and trimethylolpropane tri(meth)acrylate. The amount of the polar monomer that may be contained in the composition may be in the range of 0.1 to 30 parts by mass, and preferably 0.1 to 10 parts by mass, per 100 parts by mass of the copolymer. By using 30 parts by mass or less, the dielectric constant and dielectric dissipation factor of the obtained cured body become low. For example, in a preferred embodiment, the dielectric constant of the cured body of the copolymer is 3.5 or less, and the dielectric dissipation factor is 1.2×10 -3 It is possible to keep it below this.
[0074] <Solvent> An appropriate solvent may be added to the composition of the present invention as necessary. The solvent is used to adjust the viscosity and fluidity of the composition. As the solvent, a volatile one is preferable, and for example, cyclohexane, toluene, ethylbenzene, acetone, isopropanol, etc. are used. The solvent is used to adjust the viscosity and fluidity of the composition as a varnish. As the solvent, a solvent having a boiling point of a certain degree or more is preferable, because if the boiling point is high under atmospheric pressure, that is, if the volatility is low, the thickness of the applied film becomes uniform. The preferred boiling point is 100°C or higher, more preferably 130°C or higher and 300°C or lower under atmospheric pressure. As the solvent suitable for such a varnish, cyclohexane, toluene, xylene, mesitylene, tetralin, acetone, ethylbenzene, limonene, mixed alkanes, mixed aromatic solvents, ethylene glycol methyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether, etc. are used. In the case of a solvent, the amount of the solvent used is preferably in the range of 10 to 2000 parts by mass, more preferably 5 to 500 parts by mass, and even more preferably 10 to 300 parts by mass, per 100 parts by mass of the composition of the present invention. The solvent is preferably removed by drying treatment or the like before curing the composition.
[0075] <Filling agent> If necessary, inorganic or organic fillers may be added. These fillers are added for the purpose of controlling the thermal expansion coefficient, controlling the thermal conductivity, reducing the cost, etc., and the amount of the fillers added may be arbitrary depending on the purpose. The composition of the present invention can contain a large amount of inorganic fillers, and the amount that can be added can reach 2000 parts by mass per 100 parts by mass of copolymer. In particular, when adding inorganic fillers, it is preferable to use a known surface modifier, such as a silane coupling agent. In particular, when the objective of the present invention is to obtain a composition excellent in low dielectric constant and low dielectric loss, boron nitride (BN) is preferable as the inorganic filler. From the viewpoint of low dielectric properties, since the dielectric constant becomes particularly high when a large amount is added, it is preferable to use less than 500 parts by mass, more preferably less than 400 parts by mass of fillers per 100 parts by mass of copolymer. Furthermore, in order to improve and enhance low dielectric properties (low dielectric constant, low dielectric loss tangent), hollow fillers or fillers with many voids may be added.
[0076] Also, instead of inorganic fillers, organic fillers such as high molecular weight polyethylene, ultra-high molecular weight polyethylene, polystyrene, styrene-divinylbenzene copolymer, or fluorine-based resins can be used. The fluorine-based resin may be a known resin containing fluorine, such as PTFE (polytetrafluoroethylene) or PFA (perfluoroalkoxyalkane), and an example of such a resin is Fluon+ (registered trademark) EA-2000 from AGC. When the melting point or glass transition temperature of the organic filler is lower than the solder reflow temperature of 290°C, it is preferable from the viewpoint of heat resistance that the organic filler itself is crosslinked, and it is preferable to mix it in the form of fine particles or powder. The increase in the dielectric constant and dielectric loss tangent can also be suppressed by using these organic fillers.
[0077] On the other hand, by mixing and dispersing a high dielectric constant insulating filler having a dielectric constant at 1 GHz of preferably 3 to 10,000, more preferably 5 to 10,000, in the composition of the present invention, it is possible to prepare an insulating cured body having a high dielectric constant insulating layer having a dielectric constant of preferably 2.5 to 20, more preferably 2.8 to 10, while suppressing an increase in dielectric loss tangent (dielectric loss). By increasing the dielectric constant of a film made of an insulating cured body, it is possible to miniaturize circuits and increase the capacity of capacitors, which can contribute to miniaturization of high frequency electrical components. A high dielectric constant, low dielectric loss tangent insulating layer is suitable for applications such as capacitors, inductors for resonant circuits, filters, and antennas. Examples of the high dielectric constant insulating filler used in the present invention include inorganic fillers or metal particles that have been subjected to insulation treatment. Specific examples are known high dielectric constant inorganic fillers such as barium titanate and strontium titanate, and other examples are specifically described in, for example, JP-A-2004-087639.
[0078] <Other additives> The composition may further contain one or more selected from a flame retardant and a surface modifier. The composition of the present invention can become a matrix of a cured body, and when cured, it contains one or more selected from these fillers, flame retardants, and surface modifiers, and the cured body is likely to exhibit impact resistance and toughness even after curing, because the composition of the present invention can become a matrix of a cured body, and has excellent filling properties for other materials when cured.
[0079] <Flame retardants> A known flame retardant can be used in the composition of the present invention. From the viewpoint of maintaining a low dielectric constant and a low dielectric loss tangent, preferred flame retardants are known organic phosphorus-based flame retardants such as phosphoric acid esters or condensates thereof, known bromine-based flame retardants, and red phosphorus. In particular, among phosphoric acid esters, compounds having multiple xylenyl groups in the molecule are preferred from the viewpoint of flame retardancy and low dielectric loss tangent.
[0080] In addition to the flame retardant, antimony compounds such as antimony trioxide, antimony tetraoxide, antimony pentoxide, and sodium antimonate, or nitrogen-containing compounds such as melamine, triallyl-1,3,5-triazine-2,3,4-(1H,3H,5H)-trione, and 2,4,6-triaryloxy-1,3,5-triazine may be added as a flame retardant assistant. The total amount of these flame retardants and flame retardant assistants is usually preferably 1 to 100 parts by mass per 100 parts by mass of the composition. In addition, 30 to 200 parts by mass of a polyphenylene ether (PPE)-based resin with low dielectric constant and excellent flame retardancy may be used per 100 parts by mass of the flame retardant.
[0081] <Surface modifier> The composition of the present invention may contain various surface modifiers for the purpose of improving adhesion to fillers, copper plates, and wiring. The amount of the surface modifier used is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the composition of the present invention other than the surface modifier. Examples of the surface modifier include various silane coupling agents and titanate coupling agents. The various silane coupling agents and titanate coupling agents may be used singly or in combination.
[0082] In the present invention, the flow temperature of the curable resin or composition can be adjusted according to the purpose and molding method by changing the compounding ratio of the "resin component", "curing agent", "monomer", "solvent", "filler" or "other additives". Specifically, the composition of the present invention can take the product form of a "thermoplastic composition", a "semi-cured state (such as a B-stage sheet)", or a "varnish".
[0083] The composition of the present invention is obtained by mixing, dissolving or melting one or more selected from "resin components", "curing agents", "monomers", "solvents", "fillers" and "other additives", and further, general additives added to ordinary resins, such as lubricants, stabilizers, antioxidants, weather resistance agents, ultraviolet absorbers, etc., can be used within the scope of not impairing the object of the present invention. Any known method can be used for mixing, dissolving and melting these.
[0084] <Thermoplastic composition and molded article thereof> The composition of the present invention uses a copolymer having a molecular weight of a certain level or more, generally a weight average molecular weight of about 50,000 or more, and further contains the above-mentioned specified resin components, and can exhibit the properties of a thermoplastic resin. Therefore, under conditions that do not cause crosslinking, the composition can be molded into shapes such as sheets, tubes, strips, and pellets in a substantially uncured state by a known molding method for thermoplastic resins. The molded product may be crosslinked (cured) after or during molding.
[0085] In addition, preferred embodiments of the present composition are as follows. When the resin component contains a certain proportion or more of one or more resins selected from the above-mentioned hydrocarbon-based elastomers, polyether-based resins, olefin-aromatic vinyl compound-aromatic polyene copolymers not containing cyclic olefins, or aromatic polyene-based resins, excluding resins that are liquid at room temperature, the composition is also easily molded as a thermoplastic resin in an uncured state. The above thermoplastic compositions may be molded into various shapes such as sheets in advance at or below the action temperature of the curing agent, utilizing their thermoplasticity, and may be laminated and combined with semiconductor elements, wiring, or substrates as necessary, and then heat-cured and bonded.
[0086] The composition of the present invention may be provided in the form of a sheet obtained by molding the composition, which is heated and melted at a temperature below or below the action temperature or decomposition temperature of the curing agent, by a known method. Molding into a sheet may be performed by extrusion molding using a T-die, two-roll, or extrusion lamination onto a substrate film. In this case, the composition, the mass ratio of copolymer / monomer, or the solvent, resin component, and flame retardant are selected and adjusted so that the composition melts at or below the action temperature or decomposition temperature of the curing agent and becomes solid around room temperature. In this case, the sheet is substantially in an uncured state. After that, it is subjected to various processing and assembly steps, and finally treated at a temperature and time above the action temperature or decomposition temperature of the curing agent to completely cure. Such a method is a general technique used for ethylene-vinyl acetate resin-based crosslinking sealant sheets for solar cells (photovoltaic power generation devices).
[0087] <Molded body in semi-cured state (B-stage sheet, etc.)> The composition of the present invention can also be formed into a molded product, such as a sheet or tube, in a partially crosslinked state, for example, a state in which a part of the curing agent contained therein is reacted and semi-cured (so-called B-stage state). Here, the semi-cured state is defined as a state in which the proportion of gel content as a resin component in the composition of the present invention is more than 20% by mass and 80% by mass or less, independent of the definition of the uncured state. The gel content is a value obtained by measurement in accordance with JIS K6796:1998. For example, by adopting multiple curing agents and / or curing conditions with different curing temperatures, it is possible to semi-cure the composition and control the melt viscosity and fluidity to a B-stage state. That is, the present curable resin or composition can be molded into an easy-to-handle B-stage sheet by the first-stage curing (partial curing), which is then laminated and pressure-bonded to an electronic device or substrate, and then the second-stage curing (complete curing) can be performed to form the final shape. In this case, the composition of the composition, i.e., the mass ratio of copolymer / monomer, is selected, and if necessary, a solvent, a resin component, and a flame retardant are added, and the composition containing a curing agent such as a peroxide is partially cured, adjusted to a sheet shape (B-stage state), and after molding and assembling the device, it can be heated under pressure to completely cure. A known method can be used to partially cure the composition. For example, there is a method in which peroxides with different decomposition temperatures are used in combination, and treated for a predetermined time at a temperature at which only one of them is substantially active, to obtain a semi-cured sheet, and finally treated for a sufficient time at a temperature at which all of the curing agents are active, to completely cure.
[0088] Furthermore, the molded article may be a sheet. The sheet may be uncured (semi-cured) to the extent that the sheet shape can be maintained, or may be completely cured. The degree of curing of the composition can be quantitatively measured by a known dynamic viscoelasticity measurement method (DMA, Dynamic Mechanical Analysis).
[0089] <Varnish-like composition and molded body thereof> The composition of the present invention can be made into a viscous liquid varnish depending on its composition and blending ratio. For example, a sufficient amount of solvent and / or an appropriate amount of liquid monomer can be used to make the composition into a varnish. In particular, when the composition is used as a varnish, it is preferable to add an appropriate solvent to the composition of the present invention. The solvent is used to adjust the viscosity and fluidity of the composition as a varnish. As the solvent, a solvent having a boiling point of a certain level or higher is preferable because a high boiling point under atmospheric pressure, i.e., low volatility, leads to a uniform thickness of the applied film. A preferred boiling point is approximately 110°C or higher and 300°C or lower under atmospheric pressure. Examples of solvents suitable for such varnish include toluene, xylene, mesitylene, ethylbenzene, limonene, ethylene glycol methyl ether acetate, ethylene glycol monoethyl ether acetate, and ethylene glycol monobutyl ether. The amount of the solvent used is preferably in the range of 10 to 2000 parts by mass per 100 parts by mass of the composition of the present invention.
[0090] The varnish can be applied to or impregnated into a substrate, and the solvent or the like can be removed by drying or the like to produce an uncured or semi-cured molded body. Generally, the molded body has a sheet, film, or tape shape. In this embodiment, the obtained uncured or semi-cured molded body is cured.
[0091] <Curing> The composition can be cured by a known method, taking into consideration the curing conditions (temperature, time, pressure) of the curing agent contained therein. When the curing agent used is a peroxide, the curing conditions can be determined by taking into consideration the half-life temperature and the like disclosed for each peroxide.
[0092] <Cured product of the composition> The dielectric constant and dielectric loss tangent of the cured body obtained from the composition of the present invention are measured by a known resonator method. In this specification, the resonator method is performed at a measurement frequency of 40 GHz. The dielectric constant of the cured body is 3.5 or less, preferably 3.5 or less and 2.0 or more, and particularly preferably 3.0 or less and 2.0 or more. The dielectric loss tangent of the cured body is 0.0015 or less, and may be 0.0002 or more and 0.0015 or less, and preferably 0.0005 or more and 0.0010 or less. The volume resistivity of the cured body is preferably 1×10 15 Ω·cm or more. These values are preferred values for high frequency electrical insulating materials of, for example, 3 GHz or more. The copolymer used in the composition of the present invention is relatively soft and has a high tensile elongation, so that the cured product obtained from the composition using the copolymer has a relatively high impact resistance while exhibiting sufficient mechanical properties, and can have the characteristic of being able to follow the thermal expansion of the substrate. That is, the storage modulus of the cured product of the present invention measured at room temperature (25°C) is preferably 30 GPa or less and 0.1 GPa or more, more preferably less than 30 GPa and 0.1 GPa or more, and even more preferably 1 GPa or more and 20 GPa or less. In addition, the storage modulus measured at a high temperature (280°C) is preferably 1 MPa or more and 1 GPa or less, more preferably 5 MPa or more and 1 GPa or less, and even more preferably 10 MPa or more and 1 GPa or less. Those skilled in the art can determine the formulation of the composition having the above physical property parameters and prepare a cured product by referring to the information described in this specification and publicly known documents. The cured product obtained from the composition of the present invention can exhibit heat resistance and mechanical properties at high temperatures sufficient for practical use, even under conditions in which the monomer in the composition and the aromatic polyene as a component of the monomer are controlled to a certain level or less.
[0093] <General uses of the composition> The composition of the present invention can be used as a base material or substrate, such as a single-layer or multi-layer printed circuit board, a flexible printed circuit board, a so-called single-layer or multi-layer CCL (copper clad laminate) board, or a single-layer or multi-layer FCCL (flexible copper clad laminate) board, etc. It can also be used as various electrical insulating materials for wiring, preferably high-frequency signal wiring, such as coverlays, high-frequency transmission circuits, antennas, solder resists, build-up materials, interlayer insulating materials, bonding sheets, interlayer adhesives, and bump sheets for flip-chip bonders.
[0094] In another aspect, the present invention is directed to a composition comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer (which may be an α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer), the composition comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer (which may be an α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer), the composition having, as a cured product, a storage modulus of 10 MPa or more and 10 GPa or less at 250° C., a dielectric constant of 3.5 or more and 2.0 or more, and a dielectric loss tangent of 0.0015 or less, more preferably 1.2×10 -3 It is possible to provide an electrically insulating material which is:
[0095] In one embodiment of the present invention, a method for producing the copolymer can be provided. The method includes a method for producing the copolymer, which comprises copolymerizing each of the monomers of α-olefin, cyclic olefin, and aromatic polyene by coordination polymerization. In another embodiment, a method for producing a cured product can be provided, which includes a step of polymerizing the copolymer with a radical polymerization initiator that does not contain oxygen or nitrogen atoms in its structure and is composed only of carbon atoms and hydrogen atoms.
[0096] Coordination polymerization is a polymerization method using a coordination polymerization catalyst consisting of a transition metal compound and a cocatalyst. As the transition metal compound, a transition metal compound containing zirconium, hafnium, titanium, iron, nickel, cobalt, or palladium is preferable. In particular, for copolymerizing a cyclic olefin monomer, a transition metal compound containing zirconium, titanium, nickel, iron, or palladium is preferable. The most preferable coordination polymerization catalyst used may be a coordination polymerization catalyst consisting of a transition metal compound represented by the following general formula (1) and a cocatalyst. More preferably, the production method may include a step of copolymerizing each monomer of α-olefin, cyclic olefin, aromatic vinyl compound (if included), and aromatic polyene using a polymerization catalyst consisting of a transition metal compound represented by the following general formula (1) and a cocatalyst.
[0097] General formula (1) [ka] In the above formula, A and B are each independently a group selected from an unsubstituted or substituted cyclopentaphenanthryl group, an unsubstituted or substituted benzoindenyl group, an unsubstituted or substituted cyclopentadienyl group, or an unsubstituted or substituted indenyl group. Y is a methylene group having a bond with A and B and having hydrogen or a hydrocarbon group having 1 to 15 carbon atoms (which may contain 1 to 3 nitrogen, oxygen, sulfur, phosphorus, or silicon atoms) as a substituent, a silylene group, an ethylene group, a germylene group, or a boron residue. The substituents may be different or the same. Y may have a cyclic structure. Most preferably, Y is a methylene group having a bond with A and B and having hydrogen or a hydrocarbon group having 1 to 15 carbon atoms (which may contain 1 to 3 nitrogen, oxygen, sulfur, phosphorus, or silicon atoms) as a substituent. X is hydrogen, halogen, an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 10 carbon atoms, an alkylaryl group having 8 to 12 carbon atoms, a silyl group having a hydrocarbon substituent having 1 to 4 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, or a dialkylamide group having an alkyl substituent having 1 to 6 carbon atoms. M may be a transition metal, preferably zirconium, hafnium, or titanium.
[0098] In order to obtain a copolymer having a relatively low molecular weight and a low viscosity when made into a varnish, preferably, A and B in the above general formula (1) may each independently be a group selected from an unsubstituted or substituted cyclopentadienyl group or an unsubstituted or substituted indenyl group, and it is particularly preferable to use a transition metal compound having both an unsubstituted or substituted cyclopentadienyl group and an unsubstituted or substituted indenyl group. In order to obtain a copolymer having a high aromatic polyene content, that is, a copolymer having a high number of vinyl groups and / or vinylene groups derived from aromatic polyene monomer units per number average molecular weight, it is preferable to use a transition metal compound having at least one group selected from an unsubstituted or substituted indenyl group and an unsubstituted or substituted benzoindenyl group. In the case of a copolymer having a high aromatic polyene content, it is possible to increase the crosslink density of the cured product obtained by curing, and for example, a cured product having a storage modulus of 5 MPa or more measured at 280 ° C. can be obtained.
[0099] The cocatalyst in the polymerization catalyst of the present invention may be a known cocatalyst used in combination with a transition metal compound. Such a cocatalyst is preferably an aluminum compound or a boron compound. As the aluminum compound, alumoxane such as methylaluminoxane (also referred to as methylalumoxane or MAO) is preferably used. In addition, alkylaluminum such as triisobutylaluminum or triethylaluminum may be used. Examples of such a cocatalyst include the cocatalysts and alkylaluminum compounds described in EP 0872492A2, JP 11-130808 A, JP 9-309925 A, WO 00 / 20426, EP 0985689A1 A, and JP 6-184179 A.
[0100] Examples of boron compounds include trispentafluorophenylborane, triphenylcarbenium tetrakis(pentafluorophenyl)borate {trityltetrakis(pentafluorophenyl)borate}, lithium tetrakis(pentafluorophenyl)borate, trimethylammonium tetraphenylborate, triethylammonium tetraphenylborate, tripropylammonium tetraphenylborate, tri(n-butyl)ammonium tetraphenylborate, tri(n-butyl)ammonium tetra(p-tolyl)phenylborate, tri(n-butyl)ammonium tetra(p-ethylphenyl)borate, tri(n-butyl)ammonium tetra(pentafluorophenyl)borate, trimethylammonium tetra(p-tolyl)borate, trimethylammonium tetrakis-3,5-dimethylphenylborate, triethylammonium tetrakis-3 ,5-dimethylphenylborate, tributylammonium tetrakis-3,5-dimethylphenylborate, tributylammonium tetrakis-2,4-dimethylphenylborate, anilinium tetrakis pentafluorophenylborate, N,N'-dimethylanilinium tetraphenylborate, N,N'-dimethylanilinium tetrakis(p-tolyl)borate, N,N'-dimethylanilinium tetrakis(m-tolyl)borate, N,N'-dimethylanilinium tetrakis(2,4-dimethylphenyl)borate, N,N'-dimethylanilinium tetrakis(3,5-dimethylphenyl)borate, N,N'-dimethylanilinium tetrakis(pentafluorophenyl)borate, N,N'-diethylanilinium tetrakis(pentafluorophenyl)borate, N,N'-2,4,5-pentamethylanilinium tetraphenylborate, N,N'-2,4,5-pentaethylanilinium tetraphenylborate, di-(isopropyl)ammonium tetrakis pentafluorophenylborate, di-cyclohexylammonium tetraphenylborate, triphenylphosphonium tetraphenylborate, tri(methylphenyl)phosphonium tetraphenylborate, tri(dimethylphenyl)phosphonium tetraphenylborate, triphenylcarbenium tetrakis(p-tolyl)borate, triphenylcarbenium tetrakis(m-tolyl)borate, triphenylcarbenium tetrakis(2,4-dimethylphenyl)borate, triphenylcarbenium tetrakis(3,5-dimethylphenyl)borate, tropylium tetrakis pentafluorophenylborate, tropylium tetrakis(p-tolyl)borate, tropylium tetrakis(m-tolyl)borate, tropylium tetrakis(2,4-dimethylphenyl)borate, tropylium tetrakis(3,5-dimethylphenyl)borate, and the like. Among these, the most preferred boron promoter is a boron promoter having boron and a fluorine-substituted aromatic group bonded thereto. Examples of such a promoter include trispentafluorophenylborane, triphenylcarbenium tetrakis(pentafluorophenyl)borate {trityl tetrakis(pentafluorophenyl)borate}, lithium tetrakis(pentafluorophenyl)borate, tri(n-butyl)ammonium tetra(pentafluorophenyl)borate, tropylium tetrakispentafluorophenylborate, and N,N'-dimethylanilinium tetrakis(pentafluorophenyl)borate. Here, a phenyl group is used as an example of a fluorine-substituted aromatic group, but a fused aromatic group such as a fluorine-substituted naphthyl group can also be preferably used.
[0101] The co-catalyst is used in an aluminum atom / transition metal atomic ratio relative to the metal of the transition metal compound of 0.1 to 100,000, preferably 10 to 10,000. When the ratio is 0.1 or more, the transition metal compound can be effectively activated, and when it is 100,000 or less, it is economically advantageous. The transition metal compound and the co-catalyst may be mixed and prepared outside the polymerization equipment, or may be mixed inside the equipment during polymerization.
[0102] In particular, the aluminum atom / transition metal atomic ratio of the promoter such as alumoxane is preferably 0.1 to 100,000, more preferably 10 to 10,000, relative to the metal of the transition metal compound. If it is 0.1 or more, the transition metal compound can be effectively activated, and if it is 100,000 or less, it is economically advantageous. When a boron compound is used as the promoter, the boron atom / transition metal atomic ratio is preferably 0.1 to 100, more preferably 0.1 to 10, and most preferably in the range of 0.8 to 1.2. If it is 0.1 or more, the transition metal compound can be effectively activated, and if it is 100 or less, it is economically advantageous.
[0103] In a preferred embodiment, a cocatalyst using a boron compound as an essential component and an aluminum compound as an optional component may be used.By using a boron compound as a cocatalyst, the amount of metal components such as aluminum derived from the aluminum compound contained in the finally obtained copolymer can be reduced, and the values of the dielectric constant and dielectric loss tangent of the finally obtained uncured copolymer, or the values of the dielectric constant and dielectric loss tangent of the single cured body or composition, can be reduced to a particularly preferred range, for example, the dielectric constant of the uncured copolymer can be less than 2.3 and the dielectric loss tangent can be less than 0.0004.In addition, when a boron compound is used as a cocatalyst, the dielectric constant of the finally obtained single cured body of the copolymer can be less than 2.3 and the dielectric loss tangent can be less than 0.0004.
[0104] In an embodiment, an uncured α-olefin-cycloolefin-aromatic polyene copolymer or α-olefin-cycloolefin-aromatic vinyl compound-aromatic polyene copolymer can be provided in which the total metal content derived from the catalyst and co-catalyst is 1000 ppm or less, preferably 750 ppm or less, and most preferably 500 ppm or less. Here, the metal content derived from the catalyst and co-catalyst is defined as the total content of the transition metal element (mentioned above) used in the catalyst and the boron and / or aluminum derived from the boron compound and / or aluminum compound used in the co-catalyst, and can be defined as the total content of each of zirconium, hafnium, titanium, iron, nickel, palladium, cobalt, boron, and aluminum. Particularly preferably, the metal derived from the catalyst may be zirconium, and the metal derived from the co-catalyst may be aluminum and boron, and the metal content derived from the catalyst and co-catalyst may be the total content of each of these zirconium, aluminum, and boron. In this specification, boron is included in the category of metal. An uncured α-olefin-cyclic olefin-aromatic polyene copolymer or α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer having a total metal content of 1000 ppm or less, preferably 750 ppm or less, and most preferably 500 ppm or less, can exhibit one or more of the following properties: a dielectric constant at a measurement frequency of 40 GHz is less than 2.3, a dielectric dissipation factor at a measurement frequency of 40 GHz is less than 0.0004, and a storage modulus measured at 25° C. is 1000 MPa or more. More preferably, the uncured copolymer may have a dielectric constant at a measurement frequency of 40 GHz of less than 2.3 and a dielectric dissipation factor of less than 0.0004, and a storage modulus measured at 25° C. is 1000 MPa or more. EXAMPLES
[0105] The present invention will be described below with reference to examples, but the present invention should not be construed as being limited to the following examples.
[0106] The copolymers obtained in the synthesis examples were analyzed by the following methods. The content of vinyl group units derived from ethylene, cyclic olefin, and divinylbenzene in the copolymer is determined by: 1 H-NMR measurement and quantitative mode 13 C-NMR measurement was performed, and the measurement was performed by a known method based on the area intensity of the obtained peak. The sample was dissolved in deuterated 1,1,2,2-tetrachloroethane, and the measurement was performed at 80 to 130°C.
[0107] The molecular weight was determined as a number average molecular weight (Mn) converted to standard polystyrene using GPC (gel permeation chromatography) under the following conditions.
[0108] Column: Two TSK-GEL MultiporeHXL-M φ7.8×300 mm (Tosoh Corporation) columns were connected in series. Column temperature: 40℃ Solvent: THF Flow rate: 1.0ml / min. Detector: RI detector
[0109] <Viscosity> The viscosity of the copolymer obtained in each example was determined as follows. A 25% by weight toluene solution of each copolymer was prepared and measured at 25°C using a rotational rheometer (MCR302: manufactured by Anton Paar) at a shear rate of 1 sec -1 The value of was used.
[0110] <Gel content> The gel fraction was determined as the boiling toluene insoluble matter according to ASTM D2765-84.
[0111] <Water absorption rate> The water absorption rate was measured after immersion in pure water at 23°C for 24 hours in accordance with ASTM D570-98.
[0112] <Dielectric constant and dielectric loss (dielectric tangent)> The dielectric loss tangent was measured using the cavity resonator perturbation method (Agilent Technologies 8722ES network analyzer, Keysight Technologies split cylinder resonator 40 GHz) at 23°C and 40 GHz using a 0.1 mm x 25 mm x 30 mm sample cut from the sheet. Measurements were taken in both the uncured and cured states.
[0113] <Measurement of storage modulus> Using a dynamic viscoelasticity measuring device (TA Instruments, formerly Rheometrics RSA-G2), measurements were taken at a frequency of 1 Hz while the temperature was raised from room temperature (23°C), and the storage modulus at 25°C and 280°C were measured. Measurement samples (3mm x 40mm) were cut out from a film with a thickness of approximately 0.1mm and measured, and the storage modulus was measured in both the uncured and cured states. The glass transition temperature was also calculated from the peak top temperature of the loss tangent (tanδ) in the uncured state. The main measurement parameters involved in the measurement are as follows: Measurement frequency 1Hz Heating rate: 3℃ / min Sample measurement length: 10 mm Distortion 0.1%
[0114] <Quantitative determination of metal content in copolymer> The metal contents (in the following example, the contents of transition metal elements used in the metal catalyst, and boron and aluminum used in the promoter) were determined as follows. In addition, the contents of hafnium, titanium, iron, nickel, cobalt, and palladium were also quantified. Measurements were performed by ICP atomic emission spectrometry under the following conditions in accordance with JIS K 0116:2014. 0.5 g of the composition to be measured was weighed into a platinum crucible and incinerated on a hot plate, an electric stove, and an electric furnace (gradually heated to 600°C). 0.5 ml of HCl (1+1) (i.e., a mixture of hydrochloric acid and water in a volume ratio of 1:1) and ultrapure water were added to the residue, and after heating and dissolving, the volume was adjusted to 5 ml to prepare a test solution, which was then quantitatively analyzed by ICP emission spectrometry (using an Agilent 5110VDV).
[0115] <Example 1: Preparation of Copolymer P-1>
[0116] The raw material divinylbenzene (DVB) was "Divinylbenzene (96%)" (liquid at room temperature, a mixture of meta and para isomers containing 96% by mass of divinylbenzene, the remainder being ethylvinylbenzene) manufactured by Nippon Steel Chemical & Material Co., Ltd. The raw material was norbornene (75% concentration, toluene solution) manufactured by Maruzen Petrochemical Co., Ltd., which was added with a small amount of triisobutylaluminum (TIBA) and stirred at room temperature, and then distilled and purified under nitrogen. A 10L polymerization vessel equipped with a heating and cooling jacket and a stirrer was used. First, the inside of the polymerization vessel was thoroughly dried and replaced with nitrogen, and 3 kg of toluene, 1 kg of norbornene as a pure content, and 180 g of divinylbenzene as a pure content were charged, and about 20 L of dry nitrogen was bubbled in at an internal temperature of 50°C. Then, the inside of the polymerization vessel was replaced with ethylene gas, TIBA (manufactured by Kanto Chemical Co., Ltd.) was added in an amount of 5 mmol in terms of the moles of aluminum, and the mixture was stirred. MMAO (modified MAO) (manufactured by Toso Finechem Co., Ltd.) was then added in an amount of 50 mmol in terms of aluminum, and the mixture was stirred. The internal temperature was stabilized at 60°C, and the internal pressure of the polymerization vessel was increased to 0.4 MPaG (gauge) by supplying ethylene and stabilized. From the catalyst tank installed above the polymerization vessel, 100 μmol of rac diphenylmethylene (1-indenyl) (cyclopentadienyl) zirconium dichloride (see formula (2) below for structure) was added as a catalyst, and 100 g of a toluene solution containing 2 mmol of TIBA was added to the polymerization vessel to start polymerization. The ethylene consumed in the polymerization was gradually replenished, and the polymerization was continued while maintaining the internal temperature at 60°C and the internal pressure at 0.4MPaG. After about 2 hours of polymerization, when the amount of ethylene consumed reached 200g, the ethylene gas in the polymerization vessel was discharged and the pressure was returned to normal, and 50g of isopropanol, a polymerization terminator, was added to the polymerization vessel to terminate the polymerization. The obtained polymerization liquid was poured into a sufficiently large amount of methanol / acetone mixed solution in small amounts, and the precipitated polymer was collected by stirring and filtering, and thoroughly dried in vacuum at room temperature to obtain ethylene-norbornene-divinylbenzene copolymer P-1.
[0117] Formula (2) [ka]
[0118] <Example 2: Preparation of copolymer P-2> Polymerization was carried out in the same manner as in the synthesis of P-1, except that the amount of norbornene used was changed to 1.4 kg in terms of pure content, and the polymerization was terminated when the amount of ethylene consumed reached 100 g, thereby obtaining an ethylene-norbornene-divinylbenzene copolymer, P-2.
[0119] <Example 3: Preparation of copolymer P-3> The polymerization was carried out in the same manner as in the synthesis of P-1, except that the amounts of the raw materials were changed to 2 kg of toluene, 2 kg of norbornene as a pure content, 300 g of divinylbenzene as a pure content, and 100 mmol of MMAO (modified MAO) manufactured by Toso Finechem Co., Ltd., as aluminum. Furthermore, the catalyst used was changed to 200 μmol of dimethylmethylenebis(cyclopentadienyl)zirconium dichloride (see the structure of the following formula (3)) and 100 g of a toluene solution containing 4 mmol of TIBA. The polymerization was stopped when the amount of ethylene consumed reached 150 g, and an ethylene-norbornene-divinylbenzene copolymer, P-3, was obtained.
[0120] Formula (3) [ka]
[0121] <Example 4: Preparation of copolymer P-4> As in the synthesis of P-3, dimethylmethylenebis(cyclopentadienyl)zirconium dichloride was used as a catalyst, but instead of using MMAO as a cocatalyst, tritium tetrakis(pentafluorophenyl)borate (manufactured by Toso Finechem Co., Ltd.) was used. That is, a catalyst solution in which 125 micromoles of tritium tetrakis(pentafluorophenyl)borate were stirred and dissolved in 200 milliliters of a toluene solution containing 110 micromoles of dimethylmethylenebis(cyclopentadienyl)zirconium dichloride and 2 millimoles of triisobutylaluminum was added, and polymerization was carried out at an internal polymerization temperature of 90°C. When the amount of ethylene consumed reached 150g, the polymerization was stopped to obtain P-4, an ethylene-norbornene-divinylbenzene copolymer.
[0122] Since P-1 to P-4 obtained in each Example contained a small amount of residual monomer and solvent, they were redissolved in toluene, and the solution was poured into a sufficiently large amount of methanol / acetone mixed solution in small portions, and the precipitated polymer was stirred and filtered, and dried under vacuum at room temperature for 24 hours to obtain a purified polymer. The composition and molecular weight of the obtained P-1 to P-4 are shown in Table 1. The purified polymer was dissolved again in toluene to obtain a 50 mass% toluene solution (varnish). The varnish was applied to a smooth Teflon (registered trademark) plate with an applicator, air-dried at 25 ° C for 3 hours or more, further dried under vacuum at 120 ° C for 12 hours, and then dried under vacuum at 200 ° C for 60 minutes to obtain a transparent sheet with a thickness of 0.1 mm. This sheet was cut into pieces and the gel content was measured. From the measurement results of the gel content, it was confirmed that the sheet was in an uncured state. Using this sheet, a viscoelastic spectrum (DMA) was measured to measure the storage modulus at 25 ° C and the glass transition temperature. Using this sheet, the dielectric properties were measured. These results are shown in Table 1. It is found that the copolymer of the present invention exhibits a high glass transition temperature in an uncured state, a high storage modulus (25°C), and a low dielectric constant and dielectric loss tangent. In particular, P-4 obtained by using a boron compound as a promoter exhibits a low dielectric constant and a remarkably low dielectric loss tangent.
[0123] [Table 1a] [Table 1b]
[0124] <Example 5: Preparation of hardened sheet> Using a vessel equipped with a heating and cooling jacket and stirring blade, 100 parts by mass of P-1 (ethylene-norbornene-divinylbenzene copolymer) was heated to about 50°C in 100 parts by mass of toluene as a solvent, stirred, and the copolymer was dissolved to prepare a 50% by mass toluene solution (varnish). Furthermore, 1 part by mass of a curing agent (Perbutyl P) was added in proportion to the mass of the copolymer, dissolved, stirred, and mixed to obtain a varnish-like composition (Table 2). The obtained composition was poured into a Teflon (registered trademark) mold (frame length 7 cm, width 7 cm, thickness 0.2 mm, 0.5 mm, or 1.0 mm) on a PET sheet placed on a glass plate, thoroughly air-dried at 25°C, and then further dried in a vacuum dryer at 60°C for 3 hours or more to obtain an uncured sheet. The Teflon sheet and Teflon frame were then placed under a load of 5 MPa in a press and heated at 120°C for 30 minutes, 150°C for 30 minutes, and then 200°C for 120 minutes, after which the Teflon sheet and Teflon frame were removed to obtain a cured sheet. The gel fraction, storage modulus (25°C and 280°C), dielectric constant, dielectric dissipation factor (both measured at 23°C and 40 GHz), and water absorption of the resulting cured sheet were determined.
[0125] <Example 6: Preparation of hardened sheet> A cured sheet was obtained in the same manner as in Example 5, and the physical properties were determined in the same manner.
[0126] <Examples 7-8: Preparation of hardened sheets> P-3 and P-4, which have a glass transition temperature of 150°C or more, are more difficult to remove residual toluene from the polymer than P-1 and P-2. A cured sheet was obtained as follows, and physical properties were similarly determined. Using the same container as in Examples 5 and 6, 100 parts by mass of P-3 or P-4 (ethylene-norbornene-divinylbenzene copolymer) was heated to about 50°C in 100 parts by mass of toluene as a solvent, stirred, and the copolymer was dissolved to prepare a 50% by mass toluene solution (varnish). Furthermore, 1 part by mass of a curing agent (2,3-dimethyl-2,3-diphenylbutane, manufactured by Kanto Chemical Co., Ltd.) was added in an amount of 1 part by mass based on the copolymer mass, dissolved, stirred, and mixed to obtain a varnish-like composition (Table 2). The obtained composition was poured into a Teflon (registered trademark) mold (frame length 7 cm, width 7 cm, thickness 0.1 mm) on a PET sheet placed on a glass plate, thoroughly air-dried at 25 ° C, and then further dried at 100 ° C for 3 hours in a vacuum dryer to obtain an uncured sheet that does not substantially contain solvent. A plurality of these uncured sheets were stacked to the thickness required for each measurement, and the Teflon sheet and Teflon mold were placed under a load of 5 MPa in a vacuum press, and the sheet was heated at 250 ° C for 60 minutes, and the Teflon sheet and Teflon mold were removed to obtain a cured sheet. The gel content, storage modulus (25 ° C and 280 ° C), dielectric constant, dielectric loss tangent (both measured at 23 ° C and 40 GHz), and water absorption of the obtained cured sheet were determined.
[0127] Table 2 shows the formulation (units in the table are parts by mass) and physical properties (gel content, storage modulus at 25°C and 280°C, dielectric constant, dielectric dissipation factor, water absorption). Table 2 also shows the viscosity of a 25% by mass toluene solution (varnish) for each Example. The cured sheets obtained in Examples 5 to 8 showed a high gel content and were sufficiently cured, and the storage modulus at room temperature (25°C) was sufficiently hard for a substrate, particularly a rigid substrate. Furthermore, they showed low dielectric constant and low dielectric dissipation factor required for a high-frequency insulating material. The cured sheets obtained in Examples 5 and 6 showed a high storage modulus at high temperature (280°C) and had high mechanical properties at high temperatures. Furthermore, the viscosity of a 25% by mass toluene solution (varnish) containing the copolymer obtained in Examples 5 and 6 was 10,000 mPa·s or less in both cases. The cured sheet obtained in Example 8 showed a particularly low dielectric constant (2.1) and dielectric dissipation factor (0.0002).
[0128] [Table 2]
[0129] <Example 9: Preparation of Copolymer P-5> Polymerization, polymer recovery and post-treatment were carried out in the same manner as in the manufacturing method of P-4. However, 1.5 kg of norbornene as a pure content, 2.5 kg of toluene and 200 g of divinylbenzene as a pure content were charged. A catalyst solution was added in which 210 micromoles of tritium tetrakis(pentafluorophenyl)borate was added to 300 milliliters of a toluene solution containing 200 micromoles of dimethylmethylenebis(cyclopentadienyl)zirconium dichloride and 5 millimoles of triisobutylaluminum as a catalyst, and a catalyst solution was added, and polymerization was carried out while maintaining the polymerization temperature at 60°C and the internal pressure of the polymerization vessel at 0.15 MPaG (gauge) by supplying ethylene. During the process, the same amount of the catalyst solution as the catalyst solution was further added. When the ethylene consumption reached 100 g, the polymerization was stopped to obtain P-5, an ethylene-norbornene-divinylbenzene copolymer.
[0130] <Example 10: Preparation of copolymer P-6> Polymerization, polymer recovery and post-treatment were carried out in the same manner as in the manufacturing method of P-5. However, 1.5 kg of DMON (1,4,5,8-dimethano-1,2,3,4,4a,5,8,8a-octahydronaphthalene, Maruzen Petrochemical Co., Ltd., purity 98%) was used instead of norbornene. When the ethylene consumption reached 100 g, the polymerization was stopped to obtain P-6, an ethylene-MPNB-divinylbenzene copolymer.
[0131] <Example 11: Preparation of Copolymer P-7> Polymerization, polymer recovery and post-treatment were carried out in the same manner as in the production method of P-5. However, 1.5 kg of MPNB (methylphenylnorbornene, Maruzen Petrochemical Co., Ltd., purity 98%) was used instead of norbornene. When the ethylene consumption reached 100 g, the polymerization was stopped to obtain P-7, an ethylene-MPNB-divinylbenzene copolymer.
[0132] <Example 12: Preparation of copolymer P-8> The raw material divinylbenzene (DVB) was "Divinylbenzene (81%)" (liquid at room temperature, a mixture of meta and para isomers containing 81% by mass of divinylbenzene, the remainder being ethylvinylbenzene) manufactured by Nippon Steel Chemical & Material Co., Ltd. The raw material was norbornene (concentration 75%, toluene solution) manufactured by Maruzen Petrochemical Co., Ltd., and a small amount of triisobutylaluminum (TIBA) was added in advance and stirred at room temperature, and then distilled and purified under nitrogen. A 10L polymerization vessel equipped with a heating and cooling jacket and a stirrer was used. First, the inside of the polymerization vessel was thoroughly dried and replaced with nitrogen, and 2 kg of toluene, 1 kg of norbornene as a pure content, and 2 kg of divinylbenzene as a divinylbenzene 81% product were charged, and about 20 L of dry nitrogen was bubbled in at an internal temperature of 50°C. After that, the inside of the polymerization vessel was replaced with nitrogen gas, and 6 mmol of TIBA (manufactured by Kanto Chemical Co., Ltd.) was added as the number of moles of aluminum and stirred. After stabilizing the internal temperature at 60°C and increasing the internal pressure of the polymerization vessel to 0.1MPaG (gauge) with nitrogen, the catalyst tank installed on the polymerization vessel was used to add 210μmol of tritium tetrakis(pentafluorophenyl)borate to 100g of toluene solution containing 200μmol of dimethylmethylenebis(cyclopentadienyl)zirconium dichloride and 2mmol of TIBA as catalysts, dissolved and stirred, and the catalyst solution was added to the polymerization vessel to start polymerization. The polymerization was continued while maintaining the internal temperature at 60°C and the internal pressure at 0.1MPaG, and after 4 hours of polymerization, 50g of isopropanol, a polymerization terminator, was added to the polymerization vessel to stop the polymerization. The obtained polymerization liquid was poured into a sufficiently large amount of methanol / acetone mixed solution in small amounts, and the precipitated polymer was collected by stirring and filtering, and the polymer was thoroughly vacuum-dried at room temperature to obtain norbornene-ethylvinylbenzene-divinylbenzene copolymer P-8.
[0133] <Example 13: Preparation of Copolymer P-9> In a polymerization vessel, 2.2 kg of toluene, 1.5 kg of DMON as a pure content, 300 g of styrene, and 200 g of divinylbenzene as a pure content were charged, and copolymerization of ethylene, DMON, styrene, and divinylbenzene was carried out in the same manner as in the production method of P-6. When the ethylene consumption reached 100 g, the polymerization was stopped, and post-treatment was carried out in the same manner to obtain P-9, which is an ethylene-MPNB-ethylvinylbenzene-divinylbenzene copolymer.
[0134] The compositions, molecular weights, gel fractions, glass transition temperatures, storage moduli at 25°C, dielectric properties, and metal contents of the copolymers P-5 to P-9 are shown in Table 1. It can be seen that the copolymers P-5 to P-9 obtained using a boron compound as a promoter exhibit high glass transition temperatures in the uncured state, high storage moduli (25°C), and extremely low dielectric constants and dielectric dissipation factors.
[0135] Copolymers obtained by using DMON or MPNB as the cyclic olefin can give a high glass transition temperature even with a relatively low molar content of DMON or MPNB. That is, the DMON content of P-6 is 52 mol% in terms of molar content, and the MPNB content of P-7 is 46 mol%, which is a lower molar content than the norbornene content of P-5, which is 74 mol%, but the glass transition temperatures of P-6 and P-7 are 198°C and 186°C, respectively, which are almost the same as P-5's 190°C. When the molar content of the cyclic olefin component is relatively low, it becomes easy to replace the remaining monomer components with aromatic vinyl compound units, making it possible to give a copolymer with a higher aromatic vinyl compound unit content. That is, it is possible to increase the aromaticity of the copolymer while maintaining a high glass transition temperature, and it is preferable because it can increase the compatibility with other resins and raw materials. An example is shown in P-9. In particular, MPNB is even more preferable in this respect because the cyclic olefin itself has an aromatic group. Furthermore, copolymers obtained using DMON or MPNB as the cyclic olefin are characterized by having a low molecular weight while having a similarly high glass transition temperature. Specifically, by using DMON or MPNB as the cyclic olefin, the most preferred number average molecular weight of 12,000 or less or less than 12,000 can be easily achieved. The ease of reducing the molecular weight is preferable because it makes it easier to produce a varnish with a lower viscosity.
[0136] Since P-5 to P-9 obtained in each Example contained a small amount of residual monomer and solvent, they were redissolved in toluene, and the solution was poured into a sufficiently large amount of methanol / acetone mixed solution in small portions, and the precipitated polymer was stirred and filtered, and dried under vacuum at room temperature for 24 hours to obtain a purified polymer. The composition and molecular weight of the obtained P-5 to P-9 are shown in Table 1. The purified polymer was dissolved again in toluene to obtain a 50 mass% toluene solution (varnish). The varnish was applied to a smooth Teflon (registered trademark) plate with an applicator, air-dried at 25 ° C for 3 hours or more, further dried under vacuum at 120 ° C for 12 hours, and then dried under vacuum at 200 ° C for 60 minutes to obtain a transparent sheet with a thickness of 0.1 mm. This sheet was cut into pieces and the gel content was measured. From the measurement results of the gel content, it was confirmed that the sheet was in an uncured state. Using this sheet, a viscoelastic spectrum (DMA) was measured to measure the storage modulus at 25 ° C and the glass transition temperature. Using this sheet, the dielectric properties were measured. These results are shown in Table 1. It is found that the copolymer of the present invention exhibits a high glass transition temperature in an uncured state, a high storage modulus (25°C), and a low dielectric constant and dielectric loss tangent. It is found that P-5 to P-9 obtained by using a boron compound as a promoter exhibit a low dielectric constant and a low dielectric loss tangent.
[0137] When the norbornene-ethylvinylbenzene-divinylbenzene copolymer P-8 was subjected to 13C-NMR measurement to examine the terminal structures contained therein, no terminal structures other than those E-1 to E-8 were detected. In addition, the terminal structures characteristic of cationic polymerization described in WO 2018 / 181842 (structures designated as t1 and t2 in WO 2018 / 181842) were not detected in P-8.
Claims
1. The copolymer in an uncured state has a dielectric constant of less than 2.4 and a dielectric dissipation factor of less than 0.0008 at a measurement frequency of 40 GHz, a storage modulus of 1000 MPa or more measured at 25°C, and a number average molecular weight of 500 or more and less than 30,000, the cyclic olefin unit is a unit derived from a cyclic olefin monomer having from 7 to 30 carbon atoms, having no heteroatom and having an unsaturated hydrocarbon ring; Alpha olefin-cyclic olefin-aromatic polyene copolymer.
2. The copolymer in an uncured state has a dielectric constant of less than 2.4 and a dielectric dissipation factor of less than 0.0008 at a measurement frequency of 40 GHz, a storage modulus of 1000 MPa or more measured at 25°C, and a number average molecular weight of 500 or more and less than 30,000, the cyclic olefin unit is a unit derived from a cyclic olefin monomer having from 7 to 30 carbon atoms, having no heteroatom and having an unsaturated hydrocarbon ring; α-olefin-cyclic olefin-aromatic vinyl compound-aromatic polyene copolymer.
3. 3. The copolymer according to claim 1, wherein the copolymer in an uncured state has a dielectric constant of less than 2.3 and a dielectric loss tangent of less than 0.0004 at a measurement frequency of 40 GHz.
4. The copolymer according to claim 1 or 2, wherein the total content of metals derived from the catalyst and the co-catalyst contained in the copolymer is 1000 ppm or less.
5. 3. The copolymer according to claim 1 or 2, which, when cured alone, exhibits a dielectric constant of less than 3.5 and a dielectric loss tangent of less than 0.001 at a measurement frequency of 40 GHz.
6. 6. The copolymer according to claim 5, which, when cured alone, has a dielectric constant of less than 2.3 and a dielectric loss tangent of less than 0.0004 at a measurement frequency of 40 GHz.
7. 3. The copolymer according to claim 1, which, when cured alone, has a storage modulus of 1 MPa or more as measured at 280°C of the cured product.
8. The copolymer according to claim 7, which, when cured alone, has a storage modulus of 5 MPa or more as measured at 280°C of the cured product.
9. The copolymer according to claim 1, which satisfies all of the following (2), (4) to (6). (2) The α-olefin unit is an α-olefin having 2 to 20 carbon atoms. (4) The cyclic olefin unit is a cyclic olefin monomer unit having from 7 to 30 carbon atoms, and the content thereof is from 30% by mass to 99% by mass. (5) The aromatic polyene unit is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene monomer unit is 2 to 30 per number average molecular weight. (6) The total content of α-olefin units, cyclic olefin units, and aromatic polyene units is 100 mass%.
10. The copolymer according to claim 2, which satisfies all of the following (2) to (6): (2) The α-olefin unit is an α-olefin having 2 to 20 carbon atoms. (3) The aromatic vinyl compound unit is an aromatic vinyl compound having 8 to 20 carbon atoms. (4) The cyclic olefin unit is a cyclic olefin monomer unit having from 7 to 30 carbon atoms, and the content thereof is from 30% by mass to 99% by mass. (5) The aromatic polyene unit is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene monomer unit is 2 to 30 per number average molecular weight. (6) The total content of α-olefin units, cyclic olefin units, aromatic vinyl compound units, and aromatic polyene units is 100 mass %.
11. A copolymer according to claim 1 or 2, wherein the cyclic olefin units are units derived from a cyclic olefin monomer containing one or more norbornenes.
12. The copolymer according to claim 11, wherein the cyclic olefin unit is a unit derived from a cyclic olefin monomer including at least one selected from the group consisting of norbornene, methylphenylnorbornene, substituted norbornene other than methylphenylnorbornene, and dimethanooctahydronaphthalene.
13. The copolymer according to claim 1 or 2, which has a glass transition temperature in the range of 180° C. or higher and 300° C. or lower.
14. The copolymer according to claim 1 or 2, having a number average molecular weight of 500 or more and 15,000 or less.
15. 3. The method for producing the copolymer according to claim 1 or 2, wherein each monomer of an α-olefin, a cyclic olefin, an aromatic polyene, and, if necessary, an aromatic vinyl compound is copolymerized by coordination polymerization using a coordination polymerization catalyst.
16. The method for producing a copolymer according to claim 15, wherein the coordination polymerization catalyst is a polymerization catalyst comprising a transition metal compound represented by the following general formula (1) and a cocatalyst: General formula (1) 【Chemistry 1】 In the formula, A and B are each independently a group selected from an unsubstituted or substituted cyclopentaphenanthryl group, an unsubstituted or substituted benzoindenyl group, an unsubstituted or substituted cyclopentadienyl group, and an unsubstituted or substituted indenyl group. Y has bonds to A and B, and is a methylene group, a silylene group, an ethylene group, a germylene group, or a boron residue having hydrogen or a hydrocarbon group having 1 to 15 carbon atoms (which may contain 1 to 3 nitrogen, oxygen, sulfur, phosphorus, or silicon atoms) as a substituent. The substituents may be different or the same. Y may have a cyclic structure. X is hydrogen, halogen, an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 10 carbon atoms, an alkylaryl group having 8 to 12 carbon atoms, a silyl group having a hydrocarbon substituent having 1 to 4 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, or a dialkylamide group having an alkyl substituent having 1 to 6 carbon atoms. M is zirconium, hafnium, or titanium.
17. 17. The method for producing a copolymer according to claim 16, wherein A and B in general formula (1) are each independently a group selected from an unsubstituted or substituted cyclopentadienyl group, or an unsubstituted or substituted indenyl group.
18. 17. The process of claim 16, wherein a cocatalyst is used that comprises a boron compound.
19. The process of claim 18 , wherein the cocatalyst further comprises an aluminum compound.
20. A cured product comprising the copolymer according to claim 1 or 2.
21. The cured product according to claim 20, further having a storage modulus measured at 25°C of 1000 MPa or more and a storage modulus measured at 280°C of 1 MPa or more.
22. The cured product according to claim 20, which is an electrical insulating material.
23. A CCL substrate, an FCCL substrate, an interlayer insulating material, a coverlay, a high-frequency transmission circuit, or an antenna, comprising the cured body described in claim 22.
24. 3. A method for producing a cured product, comprising the step of polymerizing at least the copolymer according to claim 1 or 2 with a radical polymerization initiator that does not contain oxygen or nitrogen atoms in its structure and is composed only of carbon and hydrogen atoms.
Citation Information
Patent Citations
Modified rubber with high oil absorption performance and preparation process thereof
CN111909317A
Method of bonding cyclic olefin polymer
JP1991095230A
Thermosetting resin composition having low dielectric constant
JP1994192392A
Manufacture of ethylene copolymer
JP1996183813A
M-divinylbenzene-containing copolymer and its manufacturing method
JP2003026730A